Exterior material for power storage device, method for manufacturing the same, and power storage device
By adjusting the hierarchy and tensile characteristics of the battery shell material, the curling problem during the formation of deep concaves is solved, the packaging and fusion efficiency is improved, and the production efficiency is improved.
Patent Information
- Application Number
- JP2025005617
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2018-10-01
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-10
- Estimated Expiration
- 2039-09-26
AI Technical Summary
The existing battery housing materials are prone to curl edges when forming deep concaves, which affects the packaging of battery elements and the fusion of hot melt resin, resulting in reduced production efficiency.
By adjusting the hierarchy of the shell material, the slope of its stress-strain curve during tensile is controlled to 700 MPa or below 700 MPa during strain.
It effectively suppresses the curling phenomenon of battery housing material during the deep concave formation, improves the efficiency of battery packaging and hot melt resin fusion, and improves production efficiency.
Smart Images

Figure 2025061334000011 
Figure 2025061334000012 
Figure 2025061334000013
Abstract
Description
[Technical field]
[0001] The present disclosure relates to an exterior material for an electricity storage device, a manufacturing method thereof, and an electricity storage device. [Background technology]
[0002] Various types of electricity storage devices have been developed, but in all electricity storage devices, packaging materials (exterior materials) are essential components for sealing electricity storage device elements such as electrodes, electrolytes, etc. Conventionally, metallic exterior materials have been widely used as exterior materials for electricity storage devices.
[0003] Meanwhile, in recent years, various shapes as well as thinner and lighter weight are required for electricity storage devices along with the increasing performance of electric vehicles, hybrid electric vehicles, personal computers, cameras, mobile phones, etc. However, the metallic exterior materials for electricity storage devices that have been widely used in the past have the drawbacks of being difficult to keep up with the diversification of shapes and also having limitations in terms of weight reduction.
[0004] In recent years, therefore, a film-like exterior material in which a substrate, an aluminum alloy foil layer, and a heat-sealable resin layer are laminated in that order has been proposed as an exterior material for electricity storage devices that can be easily processed into a variety of shapes and can be made thinner and lighter (see, for example, Patent Document 1).
[0005] In such film-like exterior materials, recesses are generally formed by cold forming, and electricity storage device elements such as electrodes and electrolyte are placed in the space formed by the recesses. The heat-sealable resin layers are then heat-sealed to each other to obtain an electricity storage device in which the electricity storage device elements are housed inside the exterior material. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2008-287971 A Summary of the Invention [Problem to be solved by the invention]
[0007] From the standpoint of further increasing the energy density of electricity storage devices, it is necessary to form deeper recesses in film-like exterior materials by molding.
[0008] However, through investigations by the inventors of the present disclosure, it was found that when attempting to form a deeper recess in the exterior material, the peripheral edge of the recess may curl (bend) during molding, which may hinder the accommodation of the energy storage device elements and the heat fusion of the heat-sealable resin layer, thereby reducing the production efficiency of the energy storage device.
[0009] For example, in an electricity storage device used in a small device such as a personal computer, a camera, or a mobile phone, a small-area, deep recess is required to be formed in a thin exterior material, and curling due to molding can become significant. Also, in a medium- or large-sized electricity storage device such as an in-vehicle or stationary device, the size of the exterior material is large, so the curling also becomes large, and the curling has a large effect on the production efficiency of the electricity storage device.
[0010] Under these circumstances, a main object of the present disclosure is to provide a technique for suppressing curling due to molding of an exterior material for an electricity storage device. [Means for solving the problem]
[0011] The inventors of the present disclosure have conducted intensive studies to solve the above problems. According to the provisions of JIS K 7161-1:2014 (similar to ISO 527-1:2012), which has been generally used to evaluate the tensile properties of plastics, the tensile modulus of the exterior material for an electric storage device (the slope of the stress / strain curve corresponding to two points of strain of 0.05% and 0.25%) was evaluated, and the relationship between the curl due to molding of various exterior materials (hereinafter, sometimes referred to as "molding curl") and the tensile modulus was repeatedly examined. However, when a deep recess was formed in the exterior material for an electric storage device, no clear correlation was found between the molding curl and the tensile modulus. The inventors of the present disclosure considered that the cause of this was that the exterior material for an electric storage device is a laminate in which a base layer, a barrier layer, a heat-sealable resin layer, etc. are laminated, and is not a simple plastic film, and therefore the conventional evaluation method cannot be applied, and further examined the relationship between the molding curl and the tensile properties. The inventors of the present disclosure then investigated the relationship between the slope of the stress / strain curve at a stage where the strain is greater than the tensile modulus specified in JIS K 7161-1:2014 and the molding curl when the electrical storage device exterior material is deeply molded. As a result, it was found that the slope of the stress / strain curve corresponding to the two points of tensile strain of 1% and 5% in a specific direction is high in the conventional electrical storage device exterior material. It was also found that the molding curl when the electrical storage device exterior material is deeply molded can be suitably suppressed by setting the slope of the stress / strain curve corresponding to the two points of tensile strain of 1% and 5% in a specific direction to a predetermined value or less.
[0012] The present disclosure has been completed based on these findings and through further investigations. That is, the present disclosure provides the invention of the following aspects. The laminate includes at least a base layer, a barrier layer, and a heat-sealable resin layer in this order. The laminate is an exterior material for an electricity storage device, in which the gradient of a stress-strain curve corresponding to two strain points of 1% tensile strain and 5% tensile strain in the MD direction is 700 MPa or less. Effect of the Invention
[0013] According to the present disclosure, it is possible to provide a technique for suppressing curling due to molding of an exterior material for an electricity storage device. Furthermore, according to the present disclosure, it is also possible to provide a manufacturing method for an exterior material for an electricity storage device, and an electricity storage device. [Brief description of the drawings]
[0014] [Figure 1] 1 is a schematic diagram showing an example of a cross-sectional structure of an exterior material for an electricity storage device according to the present disclosure. [Diagram 2] 1 is a schematic diagram showing an example of a cross-sectional structure of an exterior material for an electricity storage device according to the present disclosure. [Diagram 3] 1 is a schematic diagram showing an example of a cross-sectional structure of an exterior material for an electricity storage device according to the present disclosure. [Figure 4] 1 is a schematic diagram showing an example of a cross-sectional structure of an exterior material for an electricity storage device according to the present disclosure. [Diagram 5] FIG. 2 is a schematic diagram for explaining a method for evaluating curling due to molding of an exterior material for an electricity storage device. [Figure 6] FIG. 2 is a schematic diagram for explaining a method for evaluating curling due to molding of an exterior material for an electricity storage device. [Figure 7] 1 is a schematic plan view of a packaging body formed from an exterior material for an electricity storage device according to the present disclosure. [Figure 8] FIG. 8 is a schematic cross-sectional view taken along line AA' in FIG. [Figure 9] 1 is a schematic plan view of a packaging body formed from an exterior material for an electricity storage device according to the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The electrical storage device packaging material of the present disclosure is composed of a laminate having at least a base layer, a barrier layer, and a heat-sealable resin layer in this order, and the laminate is characterized in that the slope of a stress-strain curve corresponding to two strain points of 1% tensile strain and 5% tensile strain in the MD direction is 700 MPa or less. By having this configuration, the electrical storage device packaging material of the present disclosure can suitably suppress curling due to molding of the electrical storage device packaging material.
[0016] The exterior material for an electricity storage device according to the present disclosure will be described in detail below. In this specification, the numerical range indicated by "to" means "not less than" or "not more than." For example, the expression "2 to 15 mm" means 2 mm or more and 15 mm or less.
[0017] 1.Layer structure and physical properties of exterior materials for energy storage devices An exterior packaging material 10 for an electricity storage device according to the present disclosure is composed of a laminate including at least a base material layer 1, a barrier layer 3, and a heat-sealable resin layer 4 in this order, as shown in, for example, Figures 1 to 4. In the exterior packaging material 10 for an electricity storage device, the base material layer 1 is the outermost layer, and the heat-sealable resin layer 4 is the innermost layer. When assembling an electricity storage device using the exterior packaging material 10 for an electricity storage device and an electricity storage device element, the heat-sealable resin layers 4 of the exterior packaging material 10 for an electricity storage device are placed opposite each other, and the electricity storage device element is housed in a space formed by heat-sealing the peripheral portions.
[0018] As shown in Figures 2 to 4, for example, the exterior material 10 for an electricity storage device may have an adhesive layer 2 between the base material layer 1 and the barrier layer 3, if necessary, for the purpose of increasing the adhesion between these layers. Also, as shown in Figures 3 and 4, for example, the exterior material 10 for an electricity storage device may have an adhesive layer 5 between the barrier layer 3 and the heat-sealable resin layer 4, if necessary, for the purpose of increasing the adhesion between these layers. Also, as shown in Figure 4, a surface coating layer 6 or the like may be provided on the outer side of the base material layer 1 (the side opposite to the heat-sealable resin layer 4 side), if necessary.
[0019] The thickness of the laminate constituting the electricity storage device exterior material 10 is not particularly limited, but the upper limit, from the viewpoints of cost reduction, energy density improvement, etc., is preferably about 180 μm or less, about 155 μm or less, and about 120 μm or less, and the lower limit, from the viewpoint of maintaining the function of the electricity storage device exterior material to protect the electricity storage device elements, is preferably about 35 μm or more, about 45 μm or more, and about 60 μm or more, and preferred ranges include, for example, about 35 to 180 μm, about 35 to 155 μm, about 35 to 120 μm, about 45 to 180 μm, about 45 to 155 μm, about 45 to 120 μm, about 60 to 180 μm, about 60 to 155 μm, and about 60 to 120 μm.
[0020] In the exterior material for an electric storage device of the present disclosure, the ratio of the total thickness of the base material layer 1, the adhesive layer 2 provided as needed, the barrier layer 3, the adhesive layer 5 provided as needed, the heat-sealable resin layer 4, and the surface coating layer 6 provided as needed to the thickness (total thickness) of the laminate constituting the exterior material for an electric storage device is preferably 90% or more, more preferably 95% or more, and even more preferably 98% or more. As a specific example, when the exterior material for an electric storage device of the present disclosure includes the base material layer 1, the adhesive layer 2, the barrier layer 3, the adhesive layer 5, and the heat-sealable resin layer 4, the ratio of the total thickness of these layers to the thickness (total thickness) of the laminate constituting the exterior material for an electric storage device 10 is preferably 90% or more, more preferably 95% or more, and even more preferably 98% or more. Furthermore, even when the exterior material for an electricity storage device of the present disclosure includes a substrate layer 1, an adhesive layer 2, a barrier layer 3, and a heat-sealable resin layer 4, the ratio of the total thickness of these layers to the thickness (total thickness) of the laminate constituting the exterior material for an electricity storage device 10 is preferably 90% or more, more preferably 95% or more, and even more preferably 98% or more.
[0021] In the exterior material for a power storage device, the MD (Machine Direction) and TD (Transverse Direction) of the barrier layer 3 described later can usually be determined in the manufacturing process. For example, when the barrier layer 3 is made of an aluminum alloy foil, linear streaks called rolling marks are formed on the surface of the aluminum alloy foil in the rolling direction (RD) of the aluminum alloy foil. Since the rolling marks extend along the rolling direction, the rolling direction of the aluminum alloy foil can be grasped by observing the surface of the aluminum alloy foil. In addition, in the manufacturing process of the laminate, the MD of the laminate usually coincides with the RD of the aluminum alloy foil, so that the MD of the laminate can be identified by observing the surface of the aluminum alloy foil of the laminate and identifying the rolling direction (RD) of the aluminum alloy foil. In addition, since the TD of the laminate is perpendicular to the MD of the laminate, the TD of the laminate can also be identified.
[0022] The laminate constituting the exterior material 10 for an electricity storage device of the present disclosure has a slope X of a stress-strain curve corresponding to two strain points of tensile strain 1% and tensile strain 5% in the MD direction. MD In order to more effectively suppress forming curl when the forming depth is increased, the slope X of the stress-strain curve is set to a predetermined value of 700 MPa or less. MD The upper limit of the stress-strain curve is, for example, about 690 MPa or less, preferably about 600 MPa or less, more preferably about 550 MPa or less, and further preferably about 510 MPa or less. MDThe lower limit of the pressure is preferably about 290 MPa or more, more preferably about 350 MPa or more, even more preferably about 380 MPa or more, even more preferably about 430 MPa or more, and even more preferably about 450 MPa or more. Preferred ranges include about 290 to 700 MPa, about 290 to 690 MPa, about 290 to 600 MPa, about 290 to 550 MPa, about 290 to 510 MPa, about 350 to 700 MPa, about 350 to 690 MPa, about 350 to 600 MPa, about 350 to 550 MPa, about 350 to 510 MPa, about 380 to 700 MPa, about 380 to 690 MPa, about 380 to 700 MPa, about 380 to 690 MPa, about 380 to 700 MPa, about 380 to 690 MPa, about 380 to 700 MPa, about 380 to 690 MPa, about 380 to 51 ... Examples of the pressure compressive strength include about 600 MPa, about 380 to 550 MPa, about 380 to 510 MPa, about 430 to 700 MPa, about 430 to 690 MPa, about 430 to 600 MPa, about 430 to 550 MPa, about 430 to 510 MPa, about 450 to 700 MPa, about 450 to 690 MPa, about 450 to 600 MPa, about 450 to 550 MPa, and about 450 to 510 MPa.
[0023] In addition, the exterior material 10 for an electricity storage device according to the present disclosure has a slope X TD Although there is no particular limitation on the stress, from the viewpoint of more effectively suppressing molding curl when the molding depth is increased, the upper limit is preferably 630 MPa or less, more preferably about 550 MPa or less, even more preferably about 500 MPa or less, and even more preferably about 440 MPa or less. Also, from the viewpoint of improving the moldability of the exterior material for an electric storage device, the slope X TDThe lower limit is preferably 240 MPa or more, more preferably about 300 MPa or more, even more preferably about 330 MPa or more, and even more preferably about 350 MPa or more. Preferred ranges include about 240 to 630 MPa, about 240 to 550 MPa, about 240 to 500 MPa, about 240 to 440 MPa, about 300 to 630 MPa, about 300 to 550 MPa, about 300 to 500 MPa, about 300 to 440 MPa, about 330 to 630 MPa, about 330 to 550 MPa, about 330 to 500 MPa, about 330 to 440 MPa, about 350 to 630 MPa, about 350 to 550 MPa, about 350 to 500 MPa, and about 350 to 440 MPa.
[0024] In addition, in the laminate constituting the exterior material 10 for a power storage device of the present disclosure, the absolute value of the difference between the slope of the stress-strain curve corresponding to two points of strain of 1% tensile strain and 5% tensile strain in the MD direction and the slope of the stress-strain curve corresponding to two points of strain of 1% tensile strain and 5% tensile strain in the TD direction is preferably about 118 MPa or less, more preferably about 85 MPa or less, even more preferably about 80 MPa or less, even more preferably about 65 MPa or less, and even more preferably about 50 MPa or less. The lower limit of the difference is, for example, 0 MPa, 5 MPa, 10 MPa, 20 MPa, etc. Preferred ranges include about 0 to 118 MPa, about 0 to 85 MPa, about 0 to 80 MPa, about 0 to 65 MPa, about 0 to 50 MPa, about 5 to 118 MPa, about 5 to 85 MPa, about 5 to 80 MPa, about 5 to 65 MPa, about 5 to 50 MPa, about 10 to 118 MPa, about 10 to 85 MPa, about 10 to 80 MPa, about 10 to 65 MPa, about 10 to 50 MPa, about 20 to 118 MPa, about 20 to 85 MPa, about 20 to 80 MPa, about 20 to 65 MPa, and about 20 to 50 MPa.
[0025] The slope X of the stress-strain curve of the exterior material 10 for an electricity storage device according to the present disclosure MD , X TDare values measured by the following method. The slope of the stress-strain curve corresponding to two points of tensile strain of 1% and 5% in the MD and TD directions of the exterior material for a power storage device is measured using a tensile tester. Note that, for conditions other than the above-mentioned range of tensile strain (measurement conditions and calculation methods other than the range of tensile strain), measurements are performed in accordance with the provisions of JIS K 7161-1:2014. The sample is a rectangle with a width of 15 mm and a length of 50 mm or more, a gauge length of 30 mm, a tensile speed of 50 mm / min, and a test environment of 23°C. In addition, in calculating the slope of the stress-strain curve at each strain, the slope is calculated using the least squares method of the regression line. Note that, if it is not possible to prepare a sample of the above shape due to circumstances such as the small size of the exterior material for a power storage device, it is also possible to measure it at a size that can be measured.
[0026] When the electricity storage device of the present disclosure is produced using the exterior material 10 for an electricity storage device of the present disclosure, if the storage section for the electricity storage device element of the package formed by the exterior material 10 for an electricity storage device of the present disclosure has a rectangular shape in plan view, it is preferable that the long side direction of the rectangular shape in plan view of the storage section corresponds to the TD direction of the exterior material 10 for an electricity storage device. MD The value of X TD When the value is higher than the value of , it is possible to manufacture an electricity storage device in which molding curl is more suitably suppressed by molding with TD as the long side (see FIG. 9). In the case of an exterior material for an electricity storage device according to the present disclosure, which is composed of a laminate including at least a base layer, a barrier layer, and a heat-sealable resin layer in this order, tension is applied in the MD direction during the manufacturing process, and therefore, the X MD The value of X TD tends to be higher than the value of
[0027] 7 and 8, in a package 100 formed from the exterior material 10 for an electricity storage device according to the present disclosure, the storage section 100a for the electricity storage device element is produced by cold forming the exterior material 10 for an electricity storage device using a forming die. The forming die is usually rectangular in plan view, and the storage section 100a is also usually rectangular in plan view. The rectangular shape may have right angles or may have rounded corners instead of right angles.
[0028] In order to set the slope of the stress-strain curve of the electrical storage device exterior material to the above value, for example, the materials, thicknesses, and various physical properties of each layer, such as the base material layer 1, barrier layer 3, heat-sealable resin layer 4, and further the adhesive layer 2, adhesive layer 5, and surface coating layer 6, constituting the electrical storage device exterior material, are adjusted. Furthermore, for example, when the base material layer 1 is formed of a resin film, it is preferable to adjust the manufacturing conditions, such as the stretching method, stretching ratio, stretching speed, cooling temperature, and heat setting temperature of the resin film, and for example, when the barrier layer is formed of a metal foil, it is preferable to adjust the manufacturing conditions, such as the stretching method, stretching ratio, stretching speed, cooling temperature, and heat setting temperature of the metal foil. In addition, since it also affects the softness of the heat-sealable resin layer 4, it is preferable to adjust the melt mass flow rate (MFR), melting point, softening point, glass transition point, film formation method, film formation temperature, film formation speed, and the type and amount of additives such as elastomers of the resin constituting the heat-sealable resin layer 4. These adjustments may be made based on known techniques.
[0029] 2. Each layer that forms the exterior material for electricity storage devices [Base material layer 1] In the present disclosure, the substrate layer 1 is a layer provided for the purpose of exhibiting the function as a substrate of the exterior material for an electricity storage device, etc. The substrate layer 1 is located on the outer layer side of the exterior material for an electricity storage device.
[0030] The material forming the base layer 1 is not particularly limited as long as it has the function of a base, that is, at least insulating properties. The base layer 1 can be formed using, for example, a resin, and the resin may contain additives described later.
[0031] When the base layer 1 is made of a resin, the base layer 1 may be, for example, a resin film made of a resin, or may be formed by applying a resin. The resin film may be an unstretched film or a stretched film. Examples of stretched films include uniaxially stretched films and biaxially stretched films, and biaxially stretched films are preferred. Examples of stretching methods for forming biaxially stretched films include sequential biaxial stretching, inflation, and simultaneous biaxial stretching. Examples of methods for applying a resin include roll coating, gravure coating, and extrusion coating.
[0032] Examples of the resin forming the base layer 1 include polyester, polyamide, polyolefin, epoxy resin, acrylic resin, fluororesin, polyurethane, silicone resin, and phenol resin, as well as modified versions of these resins. The resin forming the base layer 1 may be a copolymer of these resins or a modified version of the copolymer. Furthermore, it may be a mixture of these resins.
[0033] Of these, preferred examples of the resin forming the base layer 1 include polyester and polyamide.
[0034] Specific examples of polyesters include polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polybutylene naphthalate, polyethylene isophthalate, and copolymerized polyesters. Examples of copolymerized polyesters include copolymerized polyesters in which ethylene terephthalate is the main repeating unit. Specific examples of polyesters include copolymerized polyesters in which ethylene terephthalate is the main repeating unit and is polymerized with ethylene isophthalate (hereinafter abbreviated as polyethylene (terephthalate / isophthalate)), polyethylene (terephthalate / adipate), polyethylene (terephthalate / sodium sulfoisophthalate), polyethylene (terephthalate / sodium isophthalate), polyethylene (terephthalate / phenyl-dicarboxylate), and polyethylene (terephthalate / decane dicarboxylate). These polyesters may be used alone or in combination of two or more.
[0035] Specific examples of polyamides include aliphatic polyamides such as nylon 6, nylon 66, nylon 610, nylon 12, nylon 46, and copolymers of nylon 6 and nylon 66; hexamethylenediamine-isophthalic acid-terephthalic acid copolymer polyamides such as nylon 6I, nylon 6T, nylon 6IT, and nylon 6I6T (I represents isophthalic acid, and T represents terephthalic acid) that contain structural units derived from terephthalic acid and / or isophthalic acid, and polyamides containing aromatic compounds such as polyamide MXD6 (polymetaxylylene adipamide); alicyclic polyamides such as polyamide PACM6 (polybis(4-aminocyclohexyl)methane adipamide); polyamides copolymerized with a lactam component or an isocyanate component such as 4,4'-diphenylmethane diisocyanate; polyesteramide copolymers and polyetheresteramide copolymers that are copolymers of copolymerized polyamides with polyesters or polyalkylene ether glycols; and polyamides such as copolymers of these copolymers. These polyamides may be used alone or in combination of two or more.
[0036] The base layer 1 preferably includes at least one of a polyester film, a polyamide film, and a polyolefin film, preferably includes at least one of a stretched polyester film, a stretched polyamide film, and a stretched polyolefin film, more preferably includes at least one of a stretched polyethylene terephthalate film, a stretched polybutylene terephthalate film, a stretched nylon film, and a stretched polypropylene film, and even more preferably includes at least one of a biaxially oriented polyethylene terephthalate film, a biaxially oriented polybutylene terephthalate film, a biaxially oriented nylon film, and a biaxially oriented polypropylene film.
[0037] The base layer 1 may be a single layer, or may be composed of two or more layers. When the base layer 1 is composed of a single layer, it is preferable that the base layer 1 is composed of a single layer of the polyamide film or polyester film. When the base layer 1 is composed of two or more layers, the base layer 1 may be a laminate in which a resin film is laminated with an adhesive or the like, or may be a laminate of resin films in which resins are co-extruded to form two or more layers. In addition, a laminate of resin films in which resins are co-extruded to form two or more layers may be used as the base layer 1 without being stretched, or may be uniaxially or biaxially stretched to form the base layer 1.
[0038] In the base layer 1, specific examples of the laminate of two or more resin films include a laminate of a polyester film and a nylon film, a laminate of two or more nylon films, and a laminate of two or more polyester films, and preferably a laminate of a stretched nylon film and a stretched polyester film, a laminate of two or more stretched nylon films, and a laminate of two or more stretched polyester films. For example, when the base layer 1 is a laminate of two resin films, a laminate of a polyester resin film and a polyester resin film, a laminate of a polyamide resin film and a polyamide resin film, or a laminate of a polyester resin film and a polyamide resin film is preferred, and a laminate of a polyethylene terephthalate film and a polyethylene terephthalate film, a laminate of a nylon film and a nylon film, or a laminate of a polyethylene terephthalate film and a nylon film is more preferred. In addition, when the base layer 1 is a laminate of two or more resin films, it is preferable that the polyester resin film is located in the outermost layer of the base layer 1, because the polyester resin is less likely to discolor when, for example, an electrolyte is attached to the surface.
[0039] When the base layer 1 is a laminate of two or more resin films, the two or more resin films may be laminated via an adhesive. Preferred adhesives include the same adhesives as those exemplified in the adhesive layer 2 described later. The method for laminating two or more resin films is not particularly limited, and known methods can be adopted, such as dry lamination, sandwich lamination, extrusion lamination, and thermal lamination, and preferably dry lamination. When laminating by the dry lamination method, it is preferable to use a polyurethane adhesive as the adhesive. In this case, the thickness of the adhesive is, for example, about 2 to 5 μm. Also, an anchor coat layer may be formed on the resin film and laminated. The anchor coat layer may be the same adhesive as that exemplified in the adhesive layer 2 described later. In this case, the thickness of the anchor coat layer is, for example, about 0.01 to 1.0 μm.
[0040] Furthermore, additives such as lubricants, flame retardants, antiblocking agents, antioxidants, light stabilizers, tackifiers, and antistatic agents may be present on at least one of the surface and the interior of the base layer 1. The additives may be used alone or in combination of two or more.
[0041] In the present disclosure, from the viewpoint of improving the moldability of the exterior material for a power storage device, it is preferable that a lubricant is present on the surface of the base material layer 1. The lubricant is not particularly limited, but is preferably an amide-based lubricant. Specific examples of amide-based lubricants include, for example, saturated fatty acid amides, unsaturated fatty acid amides, substituted amides, methylol amides, saturated fatty acid bisamides, unsaturated fatty acid bisamides, fatty acid ester amides, and aromatic bisamides. Specific examples of saturated fatty acid amides include lauric acid amides, palmitic acid amides, stearic acid amides, behenic acid amides, and hydroxystearic acid amides. Specific examples of unsaturated fatty acid amides include oleic acid amides and erucic acid amides. Specific examples of substituted amides include N-oleyl palmitic acid amides, N-stearyl stearic acid amides, N-stearyl oleic acid amides, N-oleyl stearic acid amides, and N-stearyl erucic acid amides. Specific examples of methylol amides include methylol stearic acid amides. Specific examples of saturated fatty acid bisamides include methylene bisstearic acid amide, ethylene biscapric acid amide, ethylene bislauric acid amide, ethylene bisstearic acid amide, ethylene bishydroxystearic acid amide, ethylene bisbehenic acid amide, hexamethylene bisstearic acid amide, hexamethylene bisbehenic acid amide, hexamethylene hydroxystearic acid amide, N,N'-distearyl adipic acid amide, N,N'-distearyl sebacic acid amide, etc. Specific examples of unsaturated fatty acid bisamides include ethylene bisoleic acid amide, ethylene biserucic acid amide, hexamethylene bisoleic acid amide, N,N'-dioleyl adipic acid amide, N,N'-dioleyl sebacic acid amide, etc. Specific examples of fatty acid ester amides include stearamide ethyl stearate, etc. Specific examples of aromatic bisamides include m-xylylene bisstearic acid amide, m-xylylene bishydroxystearic acid amide, N,N'-distearylisophthalic acid amide, etc. The lubricant may be used alone or in combination of two or more kinds.
[0042] When a lubricant is present on the surface of the base layer 1, the amount of the lubricant is not particularly limited, but is preferably about 3 mg / m 2 More preferably, 4 to 15 mg / m 2 about 5 to 14 mg / m 2 The degree of
[0043] The lubricant present on the surface of the base layer 1 may be a lubricant exuded from the resin constituting the base layer 1, or a lubricant applied to the surface of the base layer 1.
[0044] The thickness of the substrate layer 1 is not particularly limited as long as it functions as a substrate, and may be, for example, about 3 to 50 μm, and preferably about 10 to 35 μm. When the substrate layer 1 is a laminate of two or more resin films, the thickness of each of the resin films constituting each layer is, for example, about 2 to 35 μm, and preferably about 2 to 25 μm.
[0045] [Coat layer] The exterior material for an electric storage device according to the present disclosure may have a coating layer (not shown) on the substrate layer 1 (the side opposite to the barrier layer 3 of the substrate layer 1) as necessary for the purpose of improving printability, moldability, and the like. The coating layer is provided so as to be in contact with the substrate layer 1. The thickness of the coating layer is not particularly limited as long as it exhibits the above-mentioned function as a coating layer, and may be, for example, about 0.01 to 0.40 μm, preferably about 0.01 to 0.30 μm, and more preferably about 0.1 to 0.30 μm. By having a thickness of 0.01 μm or more, a layer with a uniform film thickness can be formed on the substrate layer 1. As a result, the printability of the exterior material for an electric storage device according to the present disclosure does not become uneven, making it possible to perform uniform printing, and uniform moldability can be obtained.
[0046] Examples of resins that form the coating layer include various synthetic resins such as polyvinylidene chloride, vinylidene chloride-vinyl chloride copolymer, polyolefin, acid-modified polyolefin, polyester, epoxy resin, phenolic resin, fluororesin, cellulose ester, polyurethane, acrylic resin, polyamide, etc. Among these, polyurethane, polyester, and acrylic resin are preferred.
[0047] The coating layer may contain lubricants and additives as necessary to improve the slipperiness. Examples of the lubricants include the same lubricants as those described above. Examples of the additives include the same additives as those exemplified in the surface coating layer 6 described below. The content and particle size of these lubricants and additives are appropriately adjusted according to the thickness of the coating layer.
[0048] In addition, the exterior material for a power storage device of the present disclosure may have a coating layer (not shown) on one side (the barrier layer 3 side of the substrate layer 1 or the side opposite to the barrier layer 3 of the substrate layer 1) or both sides of the substrate layer 1, as necessary, for the purpose of improving adhesion to the layer adjacent to the substrate layer. That is, the coating layer provided on the substrate layer may be a layer intended to improve printability, formability, etc., or may be a layer intended to improve the adhesiveness of the substrate layer. Even when the coating layer is intended to improve the adhesiveness of the substrate layer, the resin forming the coating layer and the thickness are exemplified by the same resins and thicknesses as those of the coating layer described above. In addition, the above-mentioned lubricants and additives may be included, but when there is an adjacent layer on the opposite side of the substrate layer to the coating layer, it is preferable not to include lubricants or additives.
[0049] [Adhesive layer 2] In the exterior material for an electricity storage device of the present disclosure, the adhesive layer 2 is a layer that is provided between the base layer 1 and the barrier layer 3 as necessary for the purpose of increasing the adhesion between them.
[0050] The adhesive layer 2 is formed of an adhesive capable of bonding the base material layer 1 and the barrier layer 3. The adhesive used to form the adhesive layer 2 is not limited, and may be any of a chemical reaction type, a solvent volatilization type, a hot melt type, a hot pressure type, etc. Also, it may be a two-component curing adhesive (two-component adhesive), a one-component curing adhesive (one-component adhesive), or a resin that does not involve a curing reaction. Also, the adhesive layer 2 may be a single layer or multiple layers.
[0051] Specific examples of adhesive components contained in the adhesive include polyesters such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polybutylene naphthalate, polyethylene isophthalate, and copolymerized polyesters; polyethers; polyurethanes; epoxy resins; phenolic resins; polyamides such as nylon 6, nylon 66, nylon 12, and copolymerized polyamides; polyolefins, cyclic polyolefins, acid-modified polyolefins, and acid-modified cyclic polyolefins; polyvinyl acetate; cellulose; (meth)acrylic resins; polyimides; polycarbonates; amino resins such as urea resins and melamine resins; rubbers such as chloroprene rubber, nitrile rubber, and styrene-butadiene rubber; and silicone resins. These adhesive components may be used alone or in combination of two or more. Among these adhesive components, polyurethane adhesives are preferred. In addition, the adhesive strength of these adhesive component resins can be increased by using an appropriate curing agent in combination. The curing agent is selected from polyisocyanates, multifunctional epoxy resins, oxazoline group-containing polymers, polyamine resins, acid anhydrides, and the like, depending on the functional groups of the adhesive components.
[0052] Examples of polyurethane adhesives include polyurethane adhesives containing a base agent containing a polyol compound and a curing agent containing an isocyanate compound. Preferably, a two-component curing polyurethane adhesive is used in which a polyol such as polyester polyol, polyether polyol, or acrylic polyol is used as a base agent and an aromatic or aliphatic polyisocyanate is used as a curing agent. In addition, it is preferable to use a polyester polyol having a hydroxyl group on the side chain in addition to the terminal hydroxyl group of the repeating unit as the polyol compound. Since the adhesive layer 2 is formed from a polyurethane adhesive, the exterior material for the electricity storage device is given excellent electrolyte resistance, and the base layer 1 is prevented from peeling off even if the electrolyte adheres to the side surface.
[0053] In addition, the adhesive layer 2 is allowed to contain other components as long as they do not impair adhesion, and may contain a colorant, a thermoplastic elastomer, a tackifier, a filler, etc. By containing a colorant in the adhesive layer 2, the exterior material for a power storage device can be colored. As the colorant, known colorants such as pigments and dyes can be used. In addition, only one type of colorant may be used, or two or more types may be mixed and used.
[0054] The type of pigment is not particularly limited as long as it does not impair the adhesiveness of the adhesive layer 2. Examples of organic pigments include azo-based, phthalocyanine-based, quinacridone-based, anthraquinone-based, dioxazine-based, indigothioindigo-based, perinone-perylene-based, isoindolenine-based, and benzimidazolone-based pigments, while examples of inorganic pigments include carbon black-based, titanium oxide-based, cadmium-based, lead-based, chromium oxide-based, and iron-based pigments, and other examples include fine powder of mica, fish scale foil, and the like.
[0055] Among colorants, carbon black is preferred in order to give the exterior material for an electricity storage device a black appearance, for example.
[0056] The average particle size of the pigment is not particularly limited and may be, for example, about 0.05 to 5 μm, and preferably about 0.08 to 2 μm. The average particle size of the pigment is the median size measured by a laser diffraction / scattering type particle size distribution measuring device.
[0057] The content of the pigment in the adhesive layer 2 is not particularly limited as long as the exterior material for an electricity storage device is colored, and is, for example, about 5 to 60 mass %, preferably 10 to 40 mass %.
[0058] The thickness of the adhesive layer 2 is not particularly limited as long as it can bond the base layer 1 and the barrier layer 3, but the lower limit is, for example, about 1 μm or more, about 2 μm or more, and the upper limit is about 10 μm or less, about 5 μm or less, and preferred ranges are about 1 to 10 μm, about 1 to 5 μm, about 2 to 10 μm, and about 2 to 5 μm.
[0059] [Colored layer] The colored layer is a layer that is provided between the base material layer 1 and the barrier layer 3 as necessary (not shown). When the adhesive layer 2 is provided, a colored layer may be provided between the base material layer 1 and the adhesive layer 2, or between the adhesive layer 2 and the barrier layer 3. Also, a colored layer may be provided on the outside of the base material layer 1. By providing a colored layer, the exterior material for an electricity storage device can be colored.
[0060] The colored layer can be formed, for example, by applying an ink containing a colorant to the surface of the base layer 1, the surface of the adhesive layer 2, or the surface of the barrier layer 3. As the colorant, known substances such as pigments and dyes can be used. Furthermore, only one type of colorant may be used, or two or more types may be mixed together.
[0061] Specific examples of the colorant contained in the colored layer include the same as those exemplified in the section [Adhesive layer 2].
[0062] [Barrier layer 3] In the packaging material for an electricity storage device, the barrier layer 3 is a layer that at least prevents the penetration of moisture.
[0063] Examples of the barrier layer 3 include metal foils, vapor-deposited films, and resin layers having barrier properties. Examples of the vapor-deposited films include metal vapor-deposited films, inorganic oxide vapor-deposited films, and carbon-containing inorganic oxide vapor-deposited films. Examples of the resin layer include fluorine-containing resins such as polyvinylidene chloride, polymers mainly composed of chlorotrifluoroethylene (CTFE), polymers mainly composed of tetrafluoroethylene (TFE), polymers having fluoroalkyl groups, and polymers mainly composed of fluoroalkyl units, and ethylene-vinyl alcohol copolymers. Examples of the barrier layer 3 include resin films having at least one of these vapor-deposited films and resin layers. The barrier layer 3 may be provided in a plurality of layers. The barrier layer 3 preferably includes a layer made of a metal material. Specific examples of the metal material constituting the barrier layer 3 include aluminum alloys, stainless steel, titanium steel, and steel plates. When used as a metal foil, it is preferable to include at least one of aluminum alloy foil and stainless steel foil.
[0064] From the viewpoint of improving the formability of the exterior material for a power storage device, the aluminum alloy foil is preferably a soft aluminum alloy foil made of, for example, an annealed aluminum alloy, and from the viewpoint of further improving the formability, the aluminum alloy foil is preferably an iron-containing aluminum alloy foil. In the iron-containing aluminum alloy foil (100 mass%), the iron content is preferably 0.1 to 9.0 mass%, more preferably 0.5 to 2.0 mass%. By making the iron content 0.1 mass% or more, an exterior material for a power storage device having better formability can be obtained. By making the iron content 9.0 mass% or less, an exterior material for a power storage device having better flexibility can be obtained. Examples of the soft aluminum alloy foil include aluminum alloy foils having a composition specified in JIS H4160:1994 A8021H-O, JIS H4160:1994 A8079H-O, JIS H4000:2014 A8021P-O, or JIS H4000:2014 A8079P-O. Silicon, magnesium, copper, manganese, etc. may be added as necessary. Softening can be performed by annealing or the like.
[0065] Examples of the stainless steel foil include austenitic, ferritic, austenitic-ferritic, martensitic, and precipitation hardened stainless steel foils. From the viewpoint of providing an exterior material for an electricity storage device having excellent formability, the stainless steel foil is preferably made of austenitic stainless steel.
[0066] Specific examples of the austenitic stainless steel constituting the stainless steel foil include SUS304, SUS301, and SUS316L, and among these, SUS304 is particularly preferred.
[0067] In the case of a metal foil, the thickness of the barrier layer 3 should be such that it at least functions as a barrier layer that prevents moisture from penetrating, and is, for example, about 9 to 200 μm. The upper limit of the thickness of the barrier layer 3 is, for example, preferably about 85 μm or less, more preferably about 50 μm or less, even more preferably about 40 μm or less, and particularly preferably about 35 μm or less, and the lower limit is preferably about 10 μm or more, even more preferably about 20 μm or more, and more preferably about 25 μm or more. Preferred ranges of the thickness include about 10 to 85 μm, about 10 to 50 μm, about 10 to 40 μm, about 10 to 35 μm, about 20 to 85 μm, about 20 to 50 μm, about 20 to 40 μm, about 20 to 35 μm, about 25 to 85 μm, about 25 to 50 μm, about 25 to 40 μm, and about 25 to 35 μm. When the barrier layer 3 is made of an aluminum alloy foil, the above-mentioned range is particularly preferred. In particular, when the barrier layer 3 is made of a stainless steel foil, the upper limit of the thickness of the stainless steel foil is preferably about 60 μm or less, more preferably about 50 μm or less, even more preferably about 40 μm or less, even more preferably about 30 μm or less, and particularly preferably about 25 μm or less, and the lower limit is preferably about 10 μm or more, more preferably about 15 μm or more, and preferred thickness ranges include about 10 to 60 μm, about 10 to 50 μm, about 10 to 40 μm, about 10 to 30 μm, about 10 to 25 μm, about 15 to 60 μm, about 15 to 50 μm, about 15 to 40 μm, about 15 to 30 μm, and about 15 to 25 μm.
[0068] In addition, when the barrier layer 3 is a metal foil, it is preferable to provide a corrosion-resistant film at least on the surface opposite to the base layer in order to prevent dissolution and corrosion. The barrier layer 3 may have a corrosion-resistant film on both sides. Here, the corrosion-resistant film refers to a thin film that is provided with corrosion resistance by performing, for example, hydrothermal conversion treatment such as boehmite treatment, chemical conversion treatment, anodizing treatment, plating treatment such as nickel or chromium, or corrosion prevention treatment by applying a coating agent on the surface of the barrier layer. As a treatment for forming a corrosion-resistant film, one type may be performed, or two or more types may be combined. In addition to one layer, multiple layers can be formed. Furthermore, among these treatments, hydrothermal conversion treatment and anodizing treatment are treatments in which the metal foil surface is dissolved by a treatment agent to form a metal compound having excellent corrosion resistance. Note that these treatments may be included in the definition of chemical conversion treatment. In addition, when the barrier layer 3 has a corrosion-resistant film, the barrier layer 3 includes the corrosion-resistant film.
[0069] The corrosion-resistant coating prevents delamination between a barrier layer (e.g., an aluminum alloy foil) and a base layer during molding of an exterior material for an electricity storage device, prevents dissolution and corrosion of the barrier layer surface due to hydrogen fluoride produced by a reaction between an electrolyte and moisture, and in particular prevents dissolution and corrosion of aluminum oxide present on the barrier layer surface when the barrier layer is an aluminum alloy foil, and also improves the adhesion (wettability) of the barrier layer surface, thereby preventing delamination between the base layer and the barrier layer during heat sealing and between the base layer and the barrier layer during molding.
[0070] Various corrosion-resistant films formed by chemical conversion treatments are known, and mainly include corrosion-resistant films containing at least one of phosphates, chromates, fluorides, triazine thiol compounds, and rare earth oxides. Examples of chemical conversion treatments using phosphates and chromates include chromate chromate treatment, phosphoric acid chromate treatment, phosphoric acid-chromate treatment, and chromate treatment. Examples of chromium compounds used in these treatments include chromium nitrate, chromium fluoride, chromium sulfate, chromium acetate, chromium oxalate, chromium biphosphate, chromate acetyl acetate, chromium chloride, and potassium chromium sulfate. Examples of phosphorus compounds used in these treatments include sodium phosphate, potassium phosphate, ammonium phosphate, and polyphosphoric acid. Examples of chromate treatments include etching chromate treatment, electrolytic chromate treatment, and coating-type chromate treatment, and coating-type chromate treatment is preferred. In this coating type chromate treatment, at least the inner layer side of the barrier layer (e.g., aluminum alloy foil) is first degreased by a known treatment method such as an alkali immersion method, an electrolytic cleaning method, an acid cleaning method, an electrolytic acid cleaning method, or an acid activation method, and then the degreased surface is coated with a treatment liquid mainly composed of a metal phosphate such as Cr (chromium) phosphate, Ti (titanium) phosphate, Zr (zirconium) phosphate, or Zn (zinc) phosphate, or a mixture of these metal salts, or a treatment liquid mainly composed of a nonmetallic phosphate and a mixture of these nonmetallic salts, or a treatment liquid composed of a mixture of these with a synthetic resin, or the like, by a known coating method such as a roll coating method, a gravure printing method, or a dipping method, and then dried. As the treatment liquid, various solvents such as water, alcohol-based solvents, hydrocarbon-based solvents, ketone-based solvents, ester-based solvents, and ether-based solvents can be used, and water is preferred. Examples of the resin component used here include polymers such as phenolic resins and acrylic resins, and chromate treatment using an aminated phenol polymer having repeating units represented by the following general formulas (1) to (4). In the aminated phenol polymer, the repeating units represented by the following general formulas (1) to (4) may be contained alone or in any combination of two or more types.The acrylic resin is preferably polyacrylic acid, acrylic acid methacrylic acid ester copolymer, acrylic acid maleic acid copolymer, acrylic acid styrene copolymer, or a derivative thereof such as sodium salt, ammonium salt, or amine salt. In particular, a derivative of polyacrylic acid such as an ammonium salt, sodium salt, or amine salt of polyacrylic acid is preferable. In the present disclosure, polyacrylic acid means a polymer of acrylic acid. The acrylic resin is also preferably a copolymer of acrylic acid and dicarboxylic acid or dicarboxylic acid anhydride, and is also preferably an ammonium salt, sodium salt, or amine salt of a copolymer of acrylic acid and dicarboxylic acid or dicarboxylic acid anhydride. Only one type of acrylic resin may be used, or two or more types may be mixed and used.
[0071] [ka]
[0072] [ka]
[0073] [ka]
[0074] [ka]
[0075] In the general formulas (1) to (4), X represents a hydrogen atom, a hydroxy group, an alkyl group, a hydroxyalkyl group, an allyl group, or a benzyl group. 1 and R 2 In the general formulae (1) to (4), X and R each independently represent a hydroxy group, an alkyl group, or a hydroxyalkyl group. 1 and R 2Examples of the alkyl group represented by the formula (I) include linear or branched alkyl groups having 1 to 4 carbon atoms, such as a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, and a tert-butyl group. 1 and R 2 Examples of the hydroxyalkyl group represented by the formula (1) to (4) include linear or branched alkyl groups having 1 to 4 carbon atoms substituted with one hydroxy group, such as a hydroxymethyl group, a 1-hydroxyethyl group, a 2-hydroxyethyl group, a 1-hydroxypropyl group, a 2-hydroxypropyl group, a 3-hydroxypropyl group, a 1-hydroxybutyl group, a 2-hydroxybutyl group, a 3-hydroxybutyl group, and a 4-hydroxybutyl group. 1 and R 2 The alkyl group and the hydroxyalkyl group represented by the following formulae may be the same or different. In the general formulae (1) to (4), X is preferably a hydrogen atom, a hydroxy group, or a hydroxyalkyl group. The number average molecular weight of the aminated phenol polymer having the repeating units represented by the general formulae (1) to (4) is preferably about 500 to 1,000,000, for example, and more preferably about 1,000 to 20,000. The aminated phenol polymer can be prepared, for example, by polycondensing a phenol compound or a naphthol compound with formaldehyde to produce a polymer consisting of the repeating units represented by the above general formula (1) or (3), and then polycondensing the polymer with formaldehyde and an amine (R 1 R 2 NH) to the functional group (-CH 2 NR 1 R 2 The aminated phenol polymers can be used alone or in combination of two or more.
[0076] Another example of the corrosion-resistant film is a thin film formed by a coating-type corrosion prevention treatment in which a coating agent containing at least one selected from the group consisting of rare earth element oxide sol, anionic polymer, and cationic polymer is applied. The coating agent may further contain phosphoric acid or a phosphate, and a crosslinking agent for crosslinking the polymer. The rare earth element oxide sol has rare earth element oxide fine particles (for example, particles with an average particle size of 100 nm or less) dispersed in a liquid dispersion medium. Examples of rare earth element oxides include cerium oxide, yttrium oxide, neodymium oxide, and lanthanum oxide, and cerium oxide is preferred from the viewpoint of further improving adhesion. The rare earth element oxide contained in the corrosion-resistant film can be used alone or in combination of two or more. Examples of the liquid dispersion medium for the rare earth element oxide sol include various solvents such as water, alcohol-based solvents, hydrocarbon-based solvents, ketone-based solvents, ester-based solvents, and ether-based solvents, and water is preferred. As the cationic polymer, for example, polyethyleneimine, an ionic polymer complex consisting of a polymer having polyethyleneimine and a carboxylic acid, a primary amine grafted acrylic resin in which a primary amine is graft-polymerized to an acrylic main skeleton, polyallylamine or its derivative, aminated phenol, etc. are preferable. In addition, as the anionic polymer, poly(meth)acrylic acid or its salt, or a copolymer mainly composed of (meth)acrylic acid or its salt, is preferable. In addition, it is preferable that the crosslinking agent is at least one selected from the group consisting of a compound having any one of a functional group of an isocyanate group, a glycidyl group, a carboxyl group, and an oxazoline group, and a silane coupling agent. In addition, it is preferable that the phosphoric acid or the phosphoric acid salt is a condensed phosphoric acid or a condensed phosphate salt.
[0077] One example of a corrosion-resistant coating is one formed by applying a solution of fine particles of metal oxides such as aluminum oxide, titanium oxide, cerium oxide, and tin oxide, or barium sulfate dispersed in phosphoric acid to the surface of a barrier layer and baking the coating at 150°C or higher.
[0078] If necessary, the corrosion-resistant coating may have a laminated structure in which at least one of a cationic polymer and an anionic polymer is further laminated. Examples of the cationic polymer and anionic polymer include those mentioned above.
[0079] The composition of the corrosion-resistant film can be analyzed by, for example, time-of-flight secondary ion mass spectrometry.
[0080] The amount of the corrosion-resistant film formed on the surface of the barrier layer 3 in the chemical conversion treatment is not particularly limited. For example, in the case of coating-type chromate treatment, the amount of the corrosion-resistant film formed on the surface of the barrier layer 3 is preferably 1 mm. 2 It is desirable that the chromate compound is contained in an amount, calculated as chromium, of about 0.5 to 50 mg, preferably about 1.0 to 40 mg, the phosphorus compound is contained in an amount, calculated as phosphorus, of about 0.5 to 50 mg, preferably about 1.0 to 40 mg, and the aminated phenol polymer is contained in an amount, calculated as phosphorus, of about 1.0 to 200 mg, preferably about 5.0 to 150 mg, per unit weight of the ink.
[0081] The thickness of the corrosion-resistant film is not particularly limited, but is preferably about 1 nm to 20 μm, more preferably about 1 nm to 100 nm, and even more preferably about 1 nm to 50 nm, from the viewpoint of the cohesive strength of the film and the adhesive strength with the barrier layer and the heat-sealable resin layer. The thickness of the corrosion-resistant film can be measured by observation with a transmission electron microscope, or a combination of observation with a transmission electron microscope and energy dispersive X-ray spectroscopy or electron energy loss spectroscopy. Analysis of the composition of the corrosion-resistant film using time-of-flight secondary ion mass spectrometry can reveal that, for example, secondary ions consisting of Ce, P, and O (e.g., Ce 2 PO 4 + , CePO 4 - At least one of the above) and secondary ions consisting of, for example, Cr, P and O (e.g., CrPO 2 + , CrPO 4 - Peaks derived from at least one of the above are detected.
[0082] The chemical conversion treatment is carried out by applying a solution containing a compound used for forming a corrosion-resistant film to the surface of the barrier layer by a bar coating method, a roll coating method, a gravure coating method, a dipping method, or the like, and then heating the barrier layer so that the temperature of the barrier layer becomes about 70 to 200°C. In addition, before applying the chemical conversion treatment to the barrier layer, the barrier layer may be subjected to a degreasing treatment by an alkali dipping method, an electrolytic cleaning method, an acid cleaning method, an electrolytic acid cleaning method, or the like. By carrying out the degreasing treatment in this manner, it becomes possible to carry out the chemical conversion treatment of the surface of the barrier layer more efficiently. In addition, by using an acid degreasing agent in which a fluorine-containing compound is dissolved in an inorganic acid for the degreasing treatment, it is possible to not only degrease the metal foil but also form a fluoride of the metal that is in a passive state, and in such a case, only the degreasing treatment may be carried out.
[0083] [Thermal adhesive resin layer 4] In the exterior packaging material for an electricity storage device of the present disclosure, the heat-sealable resin layer 4 corresponds to the innermost layer and is a layer (sealant layer) that exhibits the function of sealing the electricity storage device elements by heat-sealing the heat-sealable resin layers to each other when the electricity storage device is assembled.
[0084] The resin constituting the heat-sealable resin layer 4 is not particularly limited as long as it is heat-sealable, but is preferably a resin containing a polyolefin skeleton, such as polyolefin or acid-modified polyolefin. The inclusion of a polyolefin skeleton in the resin constituting the heat-sealable resin layer 4 can be determined by, for example, infrared spectroscopy, gas chromatography mass spectrometry, or the like. Furthermore, when the resin constituting the heat-sealable resin layer 4 is analyzed by infrared spectroscopy, it is preferable that a peak derived from maleic anhydride is detected. For example, when maleic anhydride-modified polyolefin is measured by infrared spectroscopy, a peak derived from maleic anhydride is detected at a wave number of 1760 cm. -1 Nearby and wave number 1780cm -1A peak derived from maleic anhydride is detected near the peak. When the thermally adhesive resin layer 4 is a layer composed of maleic anhydride-modified polyolefin, a peak derived from maleic anhydride is detected by infrared spectroscopy. However, if the degree of acid modification is low, the peak becomes small and may not be detected. In that case, analysis can be performed by nuclear magnetic resonance spectroscopy.
[0085] Specific examples of polyolefins include polyethylenes such as low-density polyethylene, medium-density polyethylene, high-density polyethylene, and linear low-density polyethylene; ethylene-α-olefin copolymers; polypropylenes such as homopolypropylene, block copolymers of polypropylene (e.g., block copolymers of propylene and ethylene), and random copolymers of polypropylene (e.g., random copolymers of propylene and ethylene); propylene-α-olefin copolymers; and ethylene-butene-propylene terpolymers. Among these, polypropylene is preferred. When the polyolefin resin is a copolymer, it may be a block copolymer or a random copolymer. These polyolefin resins may be used alone or in combination of two or more.
[0086] The polyolefin may be a cyclic polyolefin. The cyclic polyolefin is a copolymer of an olefin and a cyclic monomer, and examples of the olefins constituting the cyclic polyolefin include ethylene, propylene, 4-methyl-1-pentene, styrene, butadiene, and isoprene. Examples of the cyclic monomers constituting the cyclic polyolefin include cyclic alkenes such as norbornene; and cyclic dienes such as cyclopentadiene, dicyclopentadiene, cyclohexadiene, and norbornadiene. Among these, cyclic alkenes are preferred, and norbornene is more preferred.
[0087] The acid-modified polyolefin is a polymer modified by block polymerization or graft polymerization of a polyolefin with an acid component. The polyolefin to be modified with an acid may be the above-mentioned polyolefin, a copolymer obtained by copolymerizing the above-mentioned polyolefin with a polar molecule such as acrylic acid or methacrylic acid, or a polymer such as a crosslinked polyolefin. The acid component used for the acid modification may be, for example, a carboxylic acid or an anhydride such as maleic acid, acrylic acid, itaconic acid, crotonic acid, maleic anhydride, or itaconic anhydride.
[0088] The acid-modified polyolefin may be an acid-modified cyclic polyolefin. The acid-modified cyclic polyolefin is a polymer obtained by copolymerizing a part of the monomers constituting the cyclic polyolefin by replacing it with an acid component, or by block-polymerizing or graft-polymerizing an acid component to the cyclic polyolefin. The cyclic polyolefin to be acid-modified is the same as described above. The acid component used for the acid modification is the same as the acid component used for the modification of the polyolefin.
[0089] Preferred acid-modified polyolefins include polyolefins modified with a carboxylic acid or anhydride thereof, polypropylenes modified with a carboxylic acid or anhydride thereof, maleic anhydride-modified polyolefins, and maleic anhydride-modified polypropylenes.
[0090] The thermally adhesive resin layer 4 may be formed of one type of resin alone, or may be formed of a blend polymer of two or more types of resins. Furthermore, the thermally adhesive resin layer 4 may be formed of only one layer, or may be formed of two or more layers of the same or different resins.
[0091] The heat-sealable resin layer 4 may contain a lubricant, etc., if necessary. When the heat-sealable resin layer 4 contains a lubricant, the moldability of the exterior material for a power storage device can be improved. The lubricant is not particularly limited, and a known lubricant can be used. The lubricant may be used alone or in combination of two or more kinds.
[0092] The lubricant is not particularly limited, but preferably includes an amide-based lubricant. Specific examples of the lubricant include those exemplified for the base layer 1. The lubricant may be used alone or in combination of two or more kinds.
[0093] When a lubricant is present on the surface of the heat-sealable resin layer 4, the amount of the lubricant is not particularly limited. From the viewpoint of improving the formability of the exterior material for an electrical storage device, the amount of the lubricant is preferably 10 to 50 mg / m 2 about 15 to 40 mg / m 2 The degree of
[0094] The lubricant present on the surface of the heat-fusible resin layer 4 may be a lubricant exuded from the resin constituting the heat-fusible resin layer 4, or a lubricant applied to the surface of the heat-fusible resin layer 4.
[0095] The thickness of the heat-sealable resin layer 4 is not particularly limited as long as the heat-sealable resin layers are heat-sealed to each other to exhibit the function of sealing the electricity storage device element, and may be, for example, about 100 μm or less, preferably about 85 μm or less, more preferably about 10 to 85 μm, or about 15 to 85 μm. For example, when the thickness of the adhesive layer 5 described below is greater than 10 μm, the thickness of the heat-sealable resin layer 4 is preferably about 85 μm or less, more preferably about 10 to 45 μm, or about 15 to 45 μm, and for example, when the thickness of the adhesive layer 5 described below is 10 μm or less or when the adhesive layer 5 is not provided, the thickness of the heat-sealable resin layer 4 is preferably about 20 μm or more, more preferably about 35 to 85 μm.
[0096] [Adhesive layer 5] In the packaging material for an electricity storage device of the present disclosure, the adhesive layer 5 is a layer that is provided, if necessary, between the barrier layer 3 (or the corrosion-resistant film) and the heat-sealable resin layer 4 in order to firmly bond them together.
[0097] The adhesive layer 5 is formed of a resin capable of bonding the barrier layer 3 and the heat-sealable resin layer 4. The resin used to form the adhesive layer 5 may be, for example, the same adhesive as exemplified for the adhesive layer 2. The resin used to form the adhesive layer 5 preferably contains a polyolefin skeleton, and examples thereof include the polyolefin and acid-modified polyolefin exemplified for the heat-sealable resin layer 4. The inclusion of a polyolefin skeleton in the resin constituting the adhesive layer 5 can be determined by, for example, infrared spectroscopy, gas chromatography mass spectrometry, or the like, and the analysis method is not particularly limited. In addition, when the resin constituting the adhesive layer 5 is analyzed by infrared spectroscopy, it is preferable that a peak derived from maleic anhydride is detected. For example, when maleic anhydride-modified polyolefin is measured by infrared spectroscopy, a peak derived from maleic anhydride at a wave number of 1760 cm is detected. -1 Nearby and wave number 1780cm -1 A peak derived from maleic anhydride is detected around this peak. However, if the degree of acid modification is low, the peak may be small and not detectable. In that case, analysis can be performed using nuclear magnetic resonance spectroscopy.
[0098] From the viewpoint of firmly adhering the barrier layer 3 and the heat-fusible resin layer 4, the adhesive layer 5 preferably contains an acid-modified polyolefin. Particularly preferred examples of the acid-modified polyolefin include polyolefins modified with carboxylic acid or its anhydride, polypropylenes modified with carboxylic acid or its anhydride, maleic anhydride-modified polyolefins, and maleic anhydride-modified polypropylenes.
[0099] Furthermore, from the viewpoint of reducing the thickness of the electrical storage device exterior material while providing an electrical storage device exterior material with excellent shape stability after molding, the adhesive layer 5 is more preferably a cured product of a resin composition containing an acid-modified polyolefin and a curing agent. Preferred examples of the acid-modified polyolefin include those mentioned above.
[0100] The adhesive layer 5 is preferably a cured product of a resin composition containing an acid-modified polyolefin and at least one selected from the group consisting of a compound having an isocyanate group, a compound having an oxazoline group, and a compound having an epoxy group, and is particularly preferably a cured product of a resin composition containing an acid-modified polyolefin and at least one selected from the group consisting of a compound having an isocyanate group and a compound having an epoxy group. The adhesive layer 5 is preferably at least one selected from the group consisting of polyurethane, polyester, and epoxy resin, and more preferably contains polyurethane and epoxy resin. As the polyester, for example, an amide ester resin is preferable. Amide ester resins are generally produced by the reaction of a carboxyl group and an oxazoline group. The adhesive layer 5 is more preferably a cured product of a resin composition containing at least one of these resins and the acid-modified polyolefin. In addition, if unreacted compounds such as a compound having an isocyanate group, a compound having an oxazoline group, or a curing agent such as an epoxy resin remain in the adhesive layer 5, the presence of the unreacted compounds can be confirmed by a method selected from, for example, infrared spectroscopy, Raman spectroscopy, time-of-flight secondary ion mass spectrometry (TOF-SIMS), etc.
[0101] In addition, from the viewpoint of further increasing the adhesion between the barrier layer 3 and the adhesive layer 5, the adhesive layer 5 is preferably a cured product of a resin composition containing a curing agent having at least one selected from the group consisting of an oxygen atom, a heterocycle, a C=N bond, and a COC bond. Examples of the curing agent having a heterocycle include a curing agent having an oxazoline group and a curing agent having an epoxy group. Examples of the curing agent having a C=N bond include a curing agent having an oxazoline group and a curing agent having an isocyanate group. Examples of the curing agent having a COC bond include a curing agent having an oxazoline group, a curing agent having an epoxy group, and polyurethane. It can be confirmed that the adhesive layer 5 is a cured product of a resin composition containing these curing agents by, for example, gas chromatography mass spectrometry (GCMS), infrared spectroscopy (IR), time-of-flight secondary ion mass spectrometry (TOF-SIMS), X-ray photoelectron spectroscopy (XPS), or other methods.
[0102] The compound having an isocyanate group is not particularly limited, but from the viewpoint of effectively increasing the adhesion between the barrier layer 3 and the adhesive layer 5, a polyfunctional isocyanate compound is preferably used. The polyfunctional isocyanate compound is not particularly limited as long as it is a compound having two or more isocyanate groups. Specific examples of polyfunctional isocyanate-based curing agents include pentane diisocyanate (PDI), isophorone diisocyanate (IPDI), hexamethylene diisocyanate (HDI), tolylene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), polymerized or nurated products thereof, mixtures thereof, and copolymers with other polymers. In addition, adducts, biuret products, isocyanurates, etc. are also included.
[0103] The content of the compound having an isocyanate group in the adhesive layer 5 is preferably in the range of 0.1 to 50 mass %, and more preferably in the range of 0.5 to 40 mass %, in the resin composition constituting the adhesive layer 5. This makes it possible to effectively improve the adhesion between the barrier layer 3 and the adhesive layer 5.
[0104] The compound having an oxazoline group is not particularly limited as long as it is a compound having an oxazoline skeleton. Specific examples of the compound having an oxazoline group include those having a polystyrene main chain and those having an acrylic main chain. In addition, examples of commercially available products include the Epocross series manufactured by Nippon Shokubai Co., Ltd.
[0105] The proportion of the compound having an oxazoline group in the adhesive layer 5 is preferably in the range of 0.1 to 50 mass %, and more preferably in the range of 0.5 to 40 mass %, in the resin composition constituting the adhesive layer 5. This makes it possible to effectively improve the adhesion between the barrier layer 3 and the adhesive layer 5.
[0106] An example of a compound having an epoxy group is an epoxy resin. The epoxy resin is not particularly limited as long as it is a resin capable of forming a crosslinked structure by the epoxy group present in the molecule, and a known epoxy resin can be used. The weight average molecular weight of the epoxy resin is preferably about 50 to 2000, more preferably about 100 to 1000, and further preferably about 200 to 800. In the first disclosure, the weight average molecular weight of the epoxy resin is a value measured by gel permeation chromatography (GPC) under conditions using polystyrene as a standard sample.
[0107] Specific examples of epoxy resins include glycidyl ether derivatives of trimethylolpropane, bisphenol A diglycidyl ether, modified bisphenol A diglycidyl ether, novolac glycidyl ether, glycerin polyglycidyl ether, polyglycerin polyglycidyl ether, etc. The epoxy resins may be used alone or in combination of two or more.
[0108] The ratio of the epoxy resin in the adhesive layer 5 is preferably in the range of 0.1 to 50 mass %, and more preferably in the range of 0.5 to 40 mass %, in the resin composition constituting the adhesive layer 5. This can effectively improve the adhesion between the barrier layer 3 and the adhesive layer 5.
[0109] The polyurethane is not particularly limited, and any known polyurethane can be used. The adhesive layer 5 may be, for example, a cured product of a two-component curing polyurethane.
[0110] The proportion of polyurethane in the adhesive layer 5 is preferably in the range of 0.1 to 50 mass %, and more preferably in the range of 0.5 to 40 mass %, in the resin composition constituting the adhesive layer 5. This makes it possible to effectively improve the adhesion between the barrier layer 3 and the adhesive layer 5 in an atmosphere containing a component that induces corrosion of the barrier layer, such as an electrolyte solution.
[0111] In addition, when the adhesive layer 5 is a cured product of a resin composition containing at least one selected from the group consisting of a compound having an isocyanate group, a compound having an oxazoline group, and an epoxy resin, and the acid-modified polyolefin, the acid-modified polyolefin functions as a main agent, and the compound having an isocyanate group, the compound having an oxazoline group, and the compound having an epoxy group each function as a curing agent.
[0112] The upper limit of the thickness of the adhesive layer 5 is preferably about 50 μm or less, about 40 μm or less, about 30 μm or less, about 20 μm or less, about 10 μm or less, less than about 10 μm, about 8 μm or less, about 5 μm or less, or about 3 μm or less, and the lower limit is preferably about 0.1 μm or more, or about 0.5 μm or more. The thickness range is preferably about 0.1 to 50 μm, or less than 0.1 From the viewpoint of suppressing curling due to molding of the exterior material for an electricity storage device, the thickness of the adhesive layer 5 is preferably about 0.5 μm to 10 μm, about 0.5 to 8 μm, about 0.5 to 5 μm, or about 0.5 to 3 μm. More specifically, in the case of the adhesive layer 2 or the cured product of an acid-modified polyolefin and a curing agent, from the viewpoint of suppressing curling due to molding of the exterior material for an electric storage device, the thickness is preferably about 1 to 10 μm, more preferably 1 μm or more and less than 10 μm, even more preferably about 1 to 8 μm, even more preferably about 1 to 5 μm, and even more preferably about 1 to 3 μm. In addition, in the case of using the resin exemplified in the heat-sealable resin layer 4, the thickness is preferably about 2 to 50 μm, more preferably about 10 to 40 μm. In addition, in the case of using the adhesive layer 5 or the cured product of a resin composition containing an adhesive exemplified in the adhesive layer 2 or an acid-modified polyolefin and a curing agent, the adhesive layer 5 can be formed, for example, by applying the resin composition and curing it by heating or the like. In addition, in the case of using the resin exemplified in the heat-sealable resin layer 4, the heat-sealable resin layer 4 and the adhesive layer 5 can be formed, for example, by extrusion molding.
[0113] [Surface coating layer 6] The exterior material for an electricity storage device according to the present disclosure may have a surface coating layer 6 on the substrate layer 1 (the opposite side of the substrate layer 1 to the barrier layer 3) as necessary, for the purpose of improving at least one of design, electrolyte resistance, scratch resistance, formability, etc. The surface coating layer 6 is a layer located on the outermost layer side of the exterior material for an electricity storage device when an electricity storage device is assembled using the exterior material for an electricity storage device.
[0114] The surface coating layer 6 can be formed from a resin such as polyvinylidene chloride, polyester, polyurethane, acrylic resin, or epoxy resin.
[0115] When the resin forming the surface coating layer 6 is a curable resin, the resin may be either a one-component curable type or a two-component curable type, but is preferably a two-component curable type. Examples of two-component curable resins include two-component curable polyurethane, two-component curable polyester, and two-component curable epoxy resin. Among these, two-component curable polyurethane is preferred.
[0116] Examples of two-component curing polyurethane include polyurethanes containing a base material containing a polyol compound and a curing agent containing an isocyanate compound. Preferably, two-component curing polyurethanes are used in which a polyol such as polyester polyol, polyether polyol, and acrylic polyol is used as a base material, and an aromatic or aliphatic polyisocyanate is used as a curing agent. In addition, it is preferable to use a polyester polyol having a hydroxyl group on the side chain in addition to the terminal hydroxyl group of the repeating unit as the polyol compound. Since the surface coating layer 6 is formed of polyurethane, excellent electrolyte resistance is imparted to the exterior material for the electricity storage device.
[0117] The surface coating layer 6 may contain additives such as the above-mentioned lubricant, antiblocking agent, matting agent, flame retardant, antioxidant, tackifier, and antistatic agent in at least one of the surface and the inside of the surface coating layer 6, as necessary, depending on the functionality to be provided to the surface of the surface coating layer 6. Examples of the additives include fine particles having an average particle size of about 0.5 nm to 5 μm. The average particle size of the additive is the median size measured by a laser diffraction / scattering type particle size distribution measuring device.
[0118] The additive may be either inorganic or organic. The shape of the additive is not particularly limited, and examples of the shape include spherical, fibrous, plate-like, amorphous, and scaly.
[0119] Specific examples of additives include talc, silica, graphite, kaolin, montmorillonite, mica, hydrotalcite, silica gel, zeolite, aluminum hydroxide, magnesium hydroxide, zinc oxide, magnesium oxide, aluminum oxide, neodymium oxide, antimony oxide, titanium oxide, cerium oxide, calcium sulfate, barium sulfate, calcium carbonate, calcium silicate, lithium carbonate, calcium benzoate, calcium oxalate, magnesium stearate, alumina, carbon black, carbon nanotubes, high melting point nylon, acrylate resin, crosslinked acrylic, crosslinked styrene, crosslinked polyethylene, benzoguanamine, gold, aluminum, copper, nickel, etc. The additives may be used alone or in combination of two or more. Among these additives, silica, barium sulfate, and titanium oxide are preferable from the viewpoint of dispersion stability and cost. In addition, the additives may be subjected to various surface treatments such as insulation treatment and high dispersibility treatment.
[0120] The method for forming the surface coating layer 6 is not particularly limited, and examples thereof include a method for applying a resin that forms the surface coating layer 6. When an additive is blended into the surface coating layer 6, a resin mixed with the additive may be applied.
[0121] The thickness of the surface coating layer 6 is not particularly limited as long as the surface coating layer 6 exhibits the above-mentioned functions, and may be, for example, about 0.5 to 10 μm, and preferably about 1 to 5 μm.
[0122] 3. Manufacturing method for exterior material for power storage device The method for producing the exterior material for an electricity storage device is not particularly limited as long as a laminate is obtained by laminating the layers of the exterior material for an electricity storage device of the present invention, and examples thereof include a method including a step of laminating at least the base layer 1, the barrier layer 3, and the heat-sealable resin layer 4 in this order. In the method for producing the exterior material for an electricity storage device 10 of the present disclosure, the slope of the stress-strain curve in the MD direction when the tensile elongation of the laminate constituting the exterior material for an electricity storage device 10 changes from 1% to 5% is 700 MPa or less. Details of the exterior material for an electricity storage device 10 of the present disclosure are as described above.
[0123] An example of the method for producing the exterior material for an electricity storage device of the present invention is as follows. First, a laminate (hereinafter, sometimes referred to as "laminate A") is formed in which a base layer 1, an adhesive layer 2, and a barrier layer 3 are laminated in this order. Specifically, the laminate A can be formed by a dry lamination method in which an adhesive used to form the adhesive layer 2 is applied to the base layer 1 or to the barrier layer 3, the surface of which has been chemically treated as necessary, by a coating method such as gravure coating or roll coating, and then dried, and the barrier layer 3 or base layer 1 is laminated thereon, and the adhesive layer 2 is cured.
[0124] Next, the heat-sealable resin layer 4 is laminated on the barrier layer 3 of the laminate A. When the heat-sealable resin layer 4 is directly laminated on the barrier layer 3, the heat-sealable resin layer 4 may be laminated on the barrier layer 3 of the laminate A by a method such as thermal lamination or extrusion lamination. When an adhesive layer 5 is provided between the barrier layer 3 and the heat-sealable resin layer 4, for example, (1) a method of laminating the adhesive layer 5 and the heat-sealable resin layer 4 by extruding them on the barrier layer 3 of the laminate A (co-extrusion lamination method, tandem lamination method), (2) a method of separately forming a laminate in which the adhesive layer 5 and the heat-sealable resin layer 4 are laminated, and laminating this on the barrier layer 3 of the laminate A by a thermal lamination method, or a method of forming a laminate in which the adhesive layer 5 is laminated on the barrier layer 3 of the laminate A, and laminating this on the heat-sealable resin layer 4 by a thermal lamination method. (3) a method in which a molten adhesive layer 5 is poured between the barrier layer 3 of the laminate A and a heat-sealable resin layer 4 previously formed into a sheet-like film, and the laminate A and the heat-sealable resin layer 4 are bonded together via the adhesive layer 5 (sandwich lamination method); (4) a method in which an adhesive for forming an adhesive layer 5 is solution-coated on the barrier layer 3 of the laminate A, and laminated by drying or baking, and then the heat-sealable resin layer 4 previously formed into a sheet-like film is laminated on the adhesive layer 5.
[0125] When the surface coating layer 6 is provided, the surface coating layer 6 is laminated on the surface of the base layer 1 opposite to the barrier layer 3. The surface coating layer 6 can be formed, for example, by applying the above-mentioned resin for forming the surface coating layer 6 to the surface of the base layer 1. The order of the step of laminating the barrier layer 3 on the surface of the base layer 1 and the step of laminating the surface coating layer 6 on the surface of the base layer 1 is not particularly limited. For example, after forming the surface coating layer 6 on the surface of the base layer 1, the barrier layer 3 may be formed on the surface of the base layer 1 opposite to the surface coating layer 6.
[0126] As described above, a laminate is formed which includes, in this order, the optional surface coating layer 6 / the base material layer 1 / the optional adhesive layer 2 / the barrier layer 3 / the optional adhesive layer 5 / the heat-sealable resin layer 4. In order to strengthen the adhesion of the optional adhesive layer 2 and the optional adhesive layer 5, the laminate may be subjected to a heat treatment.
[0127] In the exterior packaging material for an electricity storage device, each layer constituting the laminate may be subjected to a surface activation treatment such as corona treatment, blast treatment, oxidation treatment, ozone treatment, etc., as necessary, to improve the processability. For example, by subjecting the surface of the base layer 1 opposite to the barrier layer 3 to corona treatment, the printability of the ink on the surface of the base layer 1 can be improved.
[0128] 4. Applications of exterior materials for energy storage devices The exterior material for an electricity storage device according to the present disclosure is used in a package for hermetically housing an electricity storage device element such as a positive electrode, a negative electrode, an electrolyte, etc. That is, an electricity storage device can be formed by housing an electricity storage device element including at least a positive electrode, a negative electrode, and an electrolyte in a package formed from the exterior material for an electricity storage device according to the present disclosure.
[0129] Specifically, an electricity storage device element having at least a positive electrode, a negative electrode, and an electrolyte is covered with the exterior material for an electricity storage device of the present disclosure in such a manner that a flange portion (a region where the heat-sealable resin layers contact each other) can be formed on the periphery of the electricity storage device element with the metal terminals connected to each of the positive electrode and the negative electrode protruding outward, and the heat-sealable resin layers of the flange portion are heat-sealed to provide an electricity storage device using the exterior material for an electricity storage device. When an electricity storage device element is housed in a package formed with the exterior material for an electricity storage device of the present disclosure, the package is formed so that the heat-sealable resin portion of the exterior material for an electricity storage device of the present disclosure faces inside (the surface in contact with the electricity storage device element).
[0130] The exterior material for an electric storage device of the present disclosure can be suitably used for an electric storage device such as a battery (including a condenser, a capacitor, etc.). The exterior material for an electric storage device of the present disclosure may be used for either a primary battery or a secondary battery, but is preferably a secondary battery. The type of secondary battery to which the exterior material for an electric storage device of the present disclosure is applied is not particularly limited, and examples thereof include lithium ion batteries, lithium ion polymer batteries, all-solid-state batteries, lead-acid batteries, nickel-hydrogen batteries, nickel-cadmium batteries, nickel-iron batteries, nickel-zinc batteries, silver oxide-zinc batteries, metal-air batteries, polyvalent cation batteries, condensers, and capacitors. Among these secondary batteries, examples of suitable applications of the exterior material for an electric storage device of the present disclosure include lithium ion batteries and lithium ion polymer batteries. EXAMPLES
[0131] The present disclosure will be described in detail below with reference to examples and comparative examples. However, the present disclosure is not limited to the examples.
[0132] The biaxially oriented nylon films and aluminum alloy foils used as the substrate layer and barrier layer in the examples and comparative examples are as follows.
[0133] <Base material layer> ON1: Biaxially oriented nylon film (produced by simultaneous biaxial stretching using the inflation method, the ratio of tensile break elongation in the MD direction to the tensile break elongation in the TD direction (MD / TD) is 1.38, and the tensile break elongation in the MD direction is greater than the tensile break elongation in the TD direction) ON2: Biaxially oriented nylon film (Produced by simultaneous biaxial stretching using the inflation method. The ratio of tensile break elongation in the MD direction to the tensile break elongation in the TD direction (MD / TD) is 1.16, and the tensile break elongation in the MD direction is approximately the same as the tensile break elongation in the TD direction.) ON3: Biaxially oriented nylon film (Produced by sequential biaxial orientation using a tenter system, the ratio of tensile elongation at break in the MD direction to the tensile elongation at break in the TD direction (MD / TD) is 1.27) ON4: A biaxially oriented nylon film similar to ON3 except for the thickness, with a coating layer (a polyester polyurethane containing a lubricant applied to a thickness of 300 nm or less) on the surface opposite the barrier layer, and a coating layer (a polyester polyurethane applied to a thickness of 300 nm or less) on the surface of the barrier layer side. ON5: A film having a coating layer (polyester polyurethane applied to a thickness of 300 nm or less) on the barrier layer side of the biaxially oriented nylon film of ON3. PET: Polyethylene terephthalate film (film formed by sequential biaxial stretching using the tenter method)
[0134] <Barrier layer> ALM1: Aluminum alloy foil (aluminum alloy foil having the composition of JIS H4160:1994 A8079H-O, rolled by the roll bearing method) ALM2: Aluminum alloy foil (aluminum alloy foil with the composition of JIS H4160:1994 A8021H-O, rolled by the roll bearing method) ALM3: Aluminum alloy foil (aluminum alloy foil with the composition of JIS H4160:1994 A8021H-O, rolled by the Morgoil bearing method) ALM4: Aluminum alloy foil (aluminum alloy foil with the composition of JIS H4160:1994 A8021H-O, rolled by the Morgoil bearing method) (composition is different from ALM3)
[0135] <Manufacture of exterior materials for power storage devices> [Example 1] A barrier layer consisting of an aluminum alloy foil (ALM3, thickness 40 μm) with an acid-resistant film formed on both sides was laminated on a biaxially oriented nylon film (ON3, thickness 25 μm) as a base layer by dry lamination. Specifically, a two-liquid curing urethane adhesive (polyol compound and aromatic isocyanate compound) was applied to one side of the aluminum alloy foil with an acid-resistant film formed on both sides, and an adhesive layer (thickness 3 μm after curing) was formed on the aluminum alloy foil. Next, the adhesive layer on the aluminum alloy foil and the biaxially oriented nylon film were laminated, and then aging treatment was performed to produce a laminate of base layer / adhesive layer / barrier layer.
[0136] Next, a two-liquid curing adhesive (acid-modified polypropylene and epoxy compound) was applied to the barrier layer side of the obtained laminate, and an adhesive layer (2 μm thick after curing) was formed on the aluminum alloy foil. Next, an unstretched polypropylene film (CPP, 30 μm thick) was laminated as a heat-sealable resin layer (first layer) from above the adhesive layer by dry lamination. Next, the obtained laminate was aged and heated. Furthermore, polypropylene (PP, 50 μm thick) as a heat-sealable resin layer (second layer) was laminated by melt extrusion to laminate an adhesive layer / heat-sealable resin layer (two-layer structure) on the barrier layer, and a biaxially oriented nylon film (25 μm) / adhesive layer (3 μm) / barrier layer (40 μm) / adhesive layer (2 μm) / heat-sealable resin layer (30 μm + 50 μm) was obtained in this order as an exterior material for a storage battery device. The laminate structure of the exterior material for a storage battery device is shown in Table 1.
[0137] In addition, erucic acid amide was present as a lubricant on both sides of the exterior material for an electricity storage device to form a lubricant layer. The same applies to the following Examples 2 to 13 and Comparative Examples 1 and 2.
[0138] [Example 2] A barrier layer consisting of an aluminum alloy foil (ALM1, thickness 40 μm) with an acid-resistant film formed on both sides was laminated on a biaxially oriented nylon film (ON1, thickness 25 μm) as a base layer by dry lamination. Specifically, a two-liquid curing urethane adhesive (polyol compound and aromatic isocyanate compound) was applied to one side of the aluminum alloy foil with an acid-resistant film formed on both sides, and an adhesive layer (thickness 3 μm after curing) was formed on the aluminum alloy foil. Next, the adhesive layer on the aluminum alloy foil and the biaxially oriented nylon film were laminated, and then aging treatment was performed to produce a laminate of base layer / adhesive layer / barrier layer.
[0139] Next, a two-liquid curing adhesive (acid-modified polypropylene and epoxy compound) was applied to the barrier layer side of the obtained laminate, and an adhesive layer (4 μm thick after curing) was formed on the aluminum alloy foil. Next, an unstretched polypropylene film (CPP, thickness 30 μm) was laminated as a heat-sealable resin layer (first layer) from above the adhesive layer by dry lamination. Next, the obtained laminate was aged and heated. Furthermore, polypropylene (PP, thickness 50 μm) as a heat-sealable resin layer (second layer) was laminated by melt extrusion to laminate an adhesive layer / heat-sealable resin layer (two-layer structure) on the barrier layer, and a biaxially oriented nylon film (25 μm) / adhesive layer (3 μm) / barrier layer (40 μm) / adhesive layer (4 μm) / heat-sealable resin layer (30 μm + 50 μm) was obtained in this order as an exterior material for a storage battery device. The laminate structure of the exterior material for a storage battery device is shown in Table 1.
[0140] [Example 3] A barrier layer consisting of an aluminum alloy foil (ALM1, thickness 40 μm) with an acid-resistant film formed on both sides was laminated on a biaxially oriented nylon film (ON1, thickness 25 μm) as a base layer by dry lamination. Specifically, a two-liquid curing urethane adhesive (polyol compound and aromatic isocyanate compound) was applied to one side of the aluminum alloy foil with an acid-resistant film formed on both sides, and an adhesive layer (thickness 3 μm after curing) was formed on the aluminum alloy foil. Next, the adhesive layer on the aluminum alloy foil and the biaxially oriented nylon film were laminated, and then aging treatment was performed to produce a laminate of base layer / adhesive layer / barrier layer.
[0141] Next, a two-liquid curing adhesive (acid-modified polypropylene and epoxy compound) was applied to the barrier layer side of the obtained laminate, and an adhesive layer (4 μm thick after curing) was formed on the aluminum alloy foil. Next, an unstretched polypropylene film (CPP, 30 μm thick) was laminated as a heat-sealable resin layer (first layer) from above the adhesive layer by dry lamination. Next, the obtained laminate was aged and heated. Furthermore, polypropylene (PP, 20 μm thick) as a heat-sealable resin layer (second layer) was laminated by melt extrusion to laminate an adhesive layer / heat-sealable resin layer (two-layer structure) on the barrier layer, and a biaxially oriented nylon film (25 μm) / adhesive layer (3 μm) / barrier layer (40 μm) / adhesive layer (4 μm) / heat-sealable resin layer (30 μm + 20 μm) was laminated in this order to obtain an exterior material for a storage battery device. The laminate structure of the exterior material for a storage battery device is shown in Table 1.
[0142] [Example 4] A barrier layer consisting of an aluminum alloy foil (ALM2, thickness 35 μm) with an acid-resistant film formed on both sides was laminated by dry lamination on a biaxially oriented nylon film (ON2, thickness 15 μm) as a base layer. Specifically, a two-liquid curing urethane adhesive (polyol compound and aromatic isocyanate compound) was applied to one side of the aluminum alloy foil with an acid-resistant film formed on both sides, and an adhesive layer (thickness 3 μm after curing) was formed on the aluminum alloy foil. Next, the adhesive layer on the aluminum alloy foil and the biaxially oriented nylon film were laminated, and then aging treatment was performed to produce a laminate of base layer / adhesive layer / barrier layer.
[0143] Next, a two-liquid curing adhesive (acid-modified polypropylene and epoxy compound) was applied to the barrier layer side of the obtained laminate, and an adhesive layer (2 μm thick after curing) was formed on the aluminum alloy foil. Next, an unstretched polypropylene film (CPP, thickness 30 μm) was laminated as a heat-sealable resin layer from above the adhesive layer by dry lamination, and an adhesive layer / heat-sealable resin layer was laminated on the barrier layer. Next, the obtained laminate was aged and heated to obtain an exterior material for a storage device in which a biaxially oriented nylon film (15 μm) / adhesive layer (3 μm) / barrier layer (35 μm) / adhesive layer (2 μm) / heat-sealable resin layer (30 μm) were laminated in this order. The laminate configuration of the exterior material for a storage device is shown in Table 1.
[0144] [Example 5] A barrier layer consisting of an aluminum alloy foil (ALM4, thickness 35 μm) with an acid-resistant film formed on both sides was laminated on a biaxially oriented nylon film (ON4, thickness 20 μm) as a base layer by dry lamination. Specifically, a two-liquid curing urethane adhesive (polyol compound and aromatic isocyanate compound) was applied to one side of the aluminum alloy foil with an acid-resistant film formed on both sides, and an adhesive layer (thickness 3 μm after curing) was formed on the aluminum alloy foil. Next, the adhesive layer on the aluminum alloy foil and the biaxially oriented nylon film were laminated, and then aging treatment was performed to produce a laminate of base layer / adhesive layer / barrier layer.
[0145] Next, maleic anhydride modified polypropylene (PPa, thickness 15 μm) as an adhesive layer and polypropylene (thickness 15 μm) as a heat-sealable resin layer were co-extruded on the barrier layer side of the obtained laminate, thereby laminating an adhesive layer / heat-sealable resin layer on the barrier layer. Next, the obtained laminate was aged and heated to obtain an exterior material for a power storage device in which a biaxially oriented nylon film (20 μm) / adhesive layer (3 μm) / barrier layer (35 μm) / adhesive layer (15 μm) / heat-sealable resin layer (15 μm) were laminated in this order. The laminate configuration of the exterior material for a power storage device is shown in Table 1.
[0146] [Example 6] A barrier layer consisting of an aluminum alloy foil (ALM2, thickness 25 μm) with an acid-resistant film formed on both sides was laminated on a biaxially oriented nylon film (ON1, thickness 12 μm) as a base layer by dry lamination. Specifically, a two-liquid curing urethane adhesive (polyol compound and aromatic isocyanate compound) was applied to one side of the aluminum alloy foil with an acid-resistant film formed on both sides, and an adhesive layer (thickness 3 μm after curing) was formed on the aluminum alloy foil. Next, the adhesive layer on the aluminum alloy foil and the biaxially oriented nylon film were laminated, and then aging treatment was performed to produce a laminate of base layer / adhesive layer / barrier layer.
[0147] Next, maleic anhydride modified polypropylene (PPa, thickness 14 μm) as an adhesive layer and polypropylene (PP, thickness 10 μm) as a heat-sealable resin layer were co-extruded on the barrier layer side of the obtained laminate, thereby laminating an adhesive layer / heat-sealable resin layer on the barrier layer. Next, the obtained laminate was aged and heated to obtain an exterior material for a power storage device in which a biaxially oriented nylon film (12 μm) / adhesive layer (3 μm) / barrier layer (25 μm) / adhesive layer (14 μm) / heat-sealable resin layer (10 μm) were laminated in this order. The laminate configuration of the exterior material for a power storage device is shown in Table 1.
[0148] [Example 7] A laminated film was prepared as the substrate layer, in which a polyethylene terephthalate film (PET, thickness 12 μm) and a biaxially oriented nylon film (ON3, thickness 15 μm) were laminated with an adhesive layer (thickness 3 μm after curing) formed with a two-component curing urethane adhesive (polyol compound and aromatic isocyanate compound). Next, a barrier layer composed of an aluminum alloy foil (ALM3, thickness 40 μm) with an acid-resistant film formed on both sides was laminated on the biaxially oriented nylon film of the substrate layer by a dry lamination method. Specifically, a two-component curing urethane adhesive (polyol compound and aromatic isocyanate compound) was applied to one side of the aluminum alloy foil with an acid-resistant film formed on both sides, and an adhesive layer (thickness 3 μm after curing) was formed on the aluminum alloy foil. Next, the adhesive layer on the aluminum alloy foil and the biaxially oriented nylon film were laminated, and then aging treatment was performed to produce a substrate layer / adhesive layer / barrier layer laminate.
[0149] Next, maleic anhydride modified polypropylene (PPa, thickness 40 μm) as an adhesive layer and polypropylene (thickness 40 μm) as a heat-sealable resin layer were co-extruded on the barrier layer side of the obtained laminate, thereby laminating an adhesive layer / heat-sealable resin layer on the barrier layer. Next, the obtained laminate was aged and heated to obtain an exterior material for a power storage device in which a polyethylene terephthalate film (12 μm) / adhesive layer (3 μm) / biaxially oriented nylon film (15 μm) / adhesive layer (3 μm) / barrier layer (40 μm) / adhesive layer (40 μm) / heat-sealable resin layer (40 μm) were laminated in this order. The laminate configuration of the exterior material for a power storage device is shown in Table 1.
[0150] [Example 8] A barrier layer consisting of an aluminum alloy foil (ALM1, thickness 40 μm) with an acid-resistant film formed on both sides was laminated on a biaxially oriented nylon film (ON1, thickness 25 μm) as a base layer by dry lamination. Specifically, a two-liquid curing urethane adhesive (polyol compound and aromatic isocyanate compound) containing carbon black was applied to one side of the aluminum alloy foil with an acid-resistant film formed on both sides, forming a black adhesive layer (thickness 3 μm after curing) on the aluminum alloy foil. Next, the adhesive layer on the aluminum alloy foil and the biaxially oriented nylon film were laminated, and then aging treatment was performed to produce a laminate of base layer / adhesive layer / barrier layer.
[0151] Next, maleic anhydride modified polypropylene (PPa, thickness 23 μm) as an adhesive layer and polypropylene (PP, thickness 23 μm) as a heat-sealable resin layer were co-extruded on the barrier layer side of the obtained laminate, thereby laminating an adhesive layer / heat-sealable resin layer on the barrier layer. Next, a resin composition (thickness after curing 3 μm) containing precipitated barium sulfate with an average particle diameter of 1 μm as a filler, erucic acid amide, and an acrylate resin with an average particle diameter of 2 μm was applied by gravure coating to the surface of the biaxially oriented nylon film of the obtained laminate to form a matte surface coating layer. Next, the obtained laminate was aged and heated to obtain a black exterior material for a storage battery device in which the surface coating layer (3 μm) / biaxially oriented nylon film (25 μm) / adhesive layer (3 μm) / barrier layer (40 μm) / adhesive layer (23 μm) / heat-sealable resin layer (23 μm) were laminated in this order. The laminate structure of the exterior material for the electricity storage device is shown in Table 1.
[0152] [Example 9] A barrier layer consisting of an aluminum alloy foil (ALM3, thickness 40 μm) with an acid-resistant film formed on both sides was laminated on a biaxially oriented nylon film (ON3, thickness 25 μm) as a base layer by dry lamination. Specifically, a two-liquid curing urethane adhesive (polyol compound and aromatic isocyanate compound) was applied to one side of the aluminum alloy foil with an acid-resistant film formed on both sides, and an adhesive layer (thickness 3 μm after curing) was formed on the aluminum alloy foil. Next, the adhesive layer on the aluminum alloy foil and the biaxially oriented nylon film were laminated, and then aging treatment was performed to produce a laminate of base layer / adhesive layer / barrier layer.
[0153] Next, a two-liquid curing adhesive (acid-modified polypropylene and epoxy compound) was applied to the barrier layer side of the obtained laminate, and an adhesive layer (2 μm thick after curing) was formed on the aluminum alloy foil. Next, an unstretched polypropylene film (CPP, 30 μm thick) was laminated as a heat-sealable resin layer from above the adhesive layer by dry lamination, and an adhesive layer / heat-sealable resin layer was laminated on the barrier layer. Next, the obtained laminate was aged and heated to obtain an exterior material for a storage battery device in which a biaxially oriented nylon film (25 μm) / adhesive layer (3 μm) / barrier layer (40 μm) / adhesive layer (2 μm) / heat-sealable resin layer (30 μm) were laminated in this order. The laminate configuration of the exterior material for a storage battery device is shown in Table 1.
[0154] [Example 10] A barrier layer consisting of an aluminum alloy foil (ALM1, thickness 40 μm) with an acid-resistant film formed on both sides was laminated on a biaxially oriented nylon film (ON1, thickness 25 μm) as a base layer by dry lamination. Specifically, a two-liquid curing urethane adhesive (polyol compound and aromatic isocyanate compound) was applied to one side of the aluminum alloy foil with an acid-resistant film formed on both sides, and an adhesive layer (thickness 3 μm after curing) was formed on the aluminum alloy foil. Next, the adhesive layer on the aluminum alloy foil and the biaxially oriented nylon film were laminated, and then aging treatment was performed to produce a laminate of base layer / adhesive layer / barrier layer.
[0155] Next, a two-liquid curing adhesive (acid-modified polypropylene and epoxy compound) was applied to the barrier layer side of the obtained laminate, and an adhesive layer (4 μm thick after curing) was formed on the aluminum alloy foil. Next, an unstretched polypropylene film (CPP, thickness 30 μm) was laminated as a heat-sealable resin layer from above the adhesive layer by dry lamination, and an adhesive layer / heat-sealable resin layer was laminated on the barrier layer. Next, the obtained laminate was aged and heated to obtain an exterior material for a storage battery device in which a biaxially oriented nylon film (25 μm) / adhesive layer (3 μm) / barrier layer (40 μm) / adhesive layer (4 μm) / heat-sealable resin layer (30 μm) were laminated in this order. The laminate configuration of the exterior material for a storage battery device is shown in Table 1.
[0156] [Example 11] A barrier layer consisting of an aluminum alloy foil (ALM3, thickness 40 μm) with an acid-resistant film formed on both sides was laminated on a biaxially oriented nylon film (ON3, thickness 25 μm) as a base layer by dry lamination. Specifically, a two-liquid curing urethane adhesive (polyol compound and aromatic isocyanate compound) was applied to one side of the aluminum alloy foil with an acid-resistant film formed on both sides, and an adhesive layer (thickness 3 μm after curing) was formed on the aluminum alloy foil. Next, the adhesive layer on the aluminum alloy foil and the biaxially oriented nylon film were laminated, and then aging treatment was performed to produce a laminate of base layer / adhesive layer / barrier layer.
[0157] Next, a two-liquid curing adhesive (acid-modified polypropylene and epoxy compound) was applied to the barrier layer side of the obtained laminate, and an adhesive layer (2 μm thick after curing) was formed on the aluminum alloy foil. Next, an unstretched polypropylene film (CPP, thickness 40 μm) was laminated as a heat-sealable resin layer from above the adhesive layer by dry lamination, and an adhesive layer / heat-sealable resin layer was laminated on the barrier layer. Next, the obtained laminate was aged and heated to obtain an exterior material for a storage battery device in which a biaxially oriented nylon film (25 μm) / adhesive layer (3 μm) / barrier layer (40 μm) / adhesive layer (2 μm) / heat-sealable resin layer (40 μm) were laminated in this order. The laminate configuration of the exterior material for a storage battery device is shown in Table 1.
[0158] [Example 12] A barrier layer consisting of an aluminum alloy foil (ALM1, thickness 40 μm) with an acid-resistant film formed on both sides was laminated on a biaxially oriented nylon film (ON1, thickness 25 μm) as a base layer by dry lamination. Specifically, a two-liquid curing urethane adhesive (polyol compound and aromatic isocyanate compound) was applied to one side of the aluminum alloy foil with an acid-resistant film formed on both sides, and an adhesive layer (thickness 3 μm after curing) was formed on the aluminum alloy foil. Next, the adhesive layer on the aluminum alloy foil and the biaxially oriented nylon film were laminated, and then aging treatment was performed to produce a laminate of base layer / adhesive layer / barrier layer.
[0159] Next, maleic anhydride modified polypropylene (PPa, thickness 23 μm) as an adhesive layer and polypropylene (PP, thickness 23 μm) as a heat-sealable resin layer were co-extruded on the barrier layer side of the obtained laminate, thereby laminating an adhesive layer / heat-sealable resin layer on the barrier layer. Next, the obtained laminate was aged and heated to obtain an exterior material for a power storage device in which a biaxially oriented nylon film (25 μm) / adhesive layer (3 μm) / barrier layer (40 μm) / adhesive layer (23 μm) / heat-sealable resin layer (23 μm) were laminated in this order. The laminate configuration of the exterior material for a power storage device is shown in Table 1.
[0160] [Example 13] A barrier layer consisting of an aluminum alloy foil (ALM3, thickness 40 μm) with an acid-resistant film formed on both sides was laminated on a biaxially oriented nylon film (ON5, thickness 25 μm) as a base layer by dry lamination. Specifically, a two-liquid curing urethane adhesive (polyol compound and aromatic isocyanate compound) was applied to one side of the aluminum alloy foil with an acid-resistant film formed on both sides, and an adhesive layer (thickness 3 μm after curing) was formed on the aluminum alloy foil. Next, the adhesive layer on the aluminum alloy foil and the biaxially oriented nylon film were laminated, and then aging treatment was performed to produce a laminate of base layer / adhesive layer / barrier layer.
[0161] Next, a two-liquid curing adhesive (acid-modified polypropylene and epoxy compound) was applied to the barrier layer side of the obtained laminate, and an adhesive layer (2 μm thick after curing) was formed on the aluminum alloy foil. Next, an unstretched polypropylene film (CPP, 30 μm thick) was laminated as a heat-sealable resin layer (first layer) from above the adhesive layer by dry lamination. Next, the obtained laminate was aged and heated. Furthermore, polypropylene (PP, 50 μm thick) as a heat-sealable resin layer (second layer) was laminated by melt extrusion to laminate an adhesive layer / heat-sealable resin layer (two-layer structure) on the barrier layer, and a biaxially oriented nylon film (25 μm) / adhesive layer (3 μm) / barrier layer (40 μm) / adhesive layer (2 μm) / heat-sealable resin layer (30 μm + 50 μm) was obtained in this order as an exterior material for a storage battery device. The laminate structure of the exterior material for a storage battery device is shown in Table 1.
[0162] [Comparative Example 1] As the substrate layer, a biaxially oriented nylon film (ON1, thickness 15 μm) and a biaxially oriented nylon film (ON1, thickness 25 μm) were prepared by laminating an adhesive layer (thickness 3 μm after curing) formed by a two-component curing urethane adhesive (polyol compound and aromatic isocyanate compound). Next, a barrier layer composed of an aluminum alloy foil (ALM1, thickness 40 μm) with an acid-resistant film formed on both sides was laminated on the biaxially oriented nylon film (ON1, thickness 25 μm) of the substrate layer by a dry lamination method. Specifically, a two-component curing urethane adhesive (polyol compound and aromatic isocyanate compound) was applied to one side of the aluminum alloy foil with an acid-resistant film formed on both sides, and an adhesive layer (thickness 3 μm after curing) was formed on the aluminum alloy foil. Next, the adhesive layer on the aluminum alloy foil and the biaxially oriented nylon film were laminated, and then aging treatment was performed to produce a substrate layer / adhesive layer / barrier layer laminate.
[0163] Next, maleic anhydride modified polypropylene (PPa, thickness 23 μm) as an adhesive layer and polypropylene (PP, thickness 23 μm) as a heat-sealable resin layer were co-extruded on the barrier layer side of the obtained laminate, thereby laminating an adhesive layer / heat-sealable resin layer on the barrier layer. Next, the obtained laminate was aged and heated to obtain an exterior material for a power storage device in which a biaxially oriented nylon film (15 μm) / adhesive layer (3 μm) / biaxially oriented nylon film (25 μm) / adhesive layer (3 μm) / barrier layer (40 μm) / adhesive layer (23 μm) / heat-sealable resin layer (23 μm) were laminated in this order. The laminate configuration of the exterior material for a power storage device is shown in Table 1.
[0164] [Comparative Example 2] As the substrate layer, a biaxially oriented nylon film (ON1, thickness 15 μm) and a biaxially oriented nylon film (ON1, thickness 25 μm) were prepared by laminating an adhesive layer (thickness 3 μm after curing) formed by a two-component curing urethane adhesive (polyol compound and aromatic isocyanate compound). Next, a barrier layer composed of an aluminum alloy foil (ALM2, thickness 35 μm) having an acid-resistant film formed on both sides was laminated on the biaxially oriented nylon film (ON1, thickness 25 μm) of the substrate layer by a dry lamination method. Specifically, a two-component curing urethane adhesive (polyol compound and aromatic isocyanate compound) was applied to one side of the aluminum alloy foil having an acid-resistant film formed on both sides, and an adhesive layer (thickness 3 μm after curing) was formed on the aluminum alloy foil. Next, the adhesive layer on the aluminum alloy foil and the biaxially oriented nylon film were laminated, and then aging treatment was performed to produce a substrate layer / adhesive layer / barrier layer laminate.
[0165] Next, maleic anhydride modified polypropylene (PPa, thickness 23 μm) as an adhesive layer and polypropylene (PP, thickness 23 μm) as a heat-sealable resin layer were co-extruded on the barrier layer side of the obtained laminate, thereby laminating an adhesive layer / heat-sealable resin layer on the barrier layer. Next, the obtained laminate was aged and heated to obtain an exterior material for a power storage device in which a biaxially oriented nylon film (15 μm) / adhesive layer (3 μm) / biaxially oriented nylon film (25 μm) / adhesive layer (3 μm) / barrier layer (35 μm) / adhesive layer (23 μm) / heat-sealable resin layer (23 μm) were laminated in this order. The laminate configuration of the exterior material for a power storage device is shown in Table 1.
[0166] [Table 1]
[0167] In Table 1, ON means biaxially oriented nylon film, PET means polyethylene terephthalate film, DL means adhesive layer or bonding layer formed by dry lamination method, ALM means aluminum alloy foil, CPP means unoriented polypropylene film, PPa means maleic anhydride modified polypropylene, PP means polypropylene, and Matt means matte surface coating layer. The numbers in parentheses indicate the thickness of each layer.
[0168] <Slope of stress-strain curve> The slope of the stress-strain curve corresponding to the two points of tensile strain of 0.05% and 0.25% and the slope of the stress-strain curve corresponding to the two points of tensile strain of 1% and 5% were measured using a tensile tester (Shimadzu Corporation, AG-Xplus (trade name)). The conditions other than the above-mentioned range of strain were measured in accordance with the provisions of JIS K 7161-1:2014. The sample was a rectangle with a width of 15 mm and a length of 50 mm or more (if the measurement was in the MD direction, the length direction was MD, and if the measurement was in the TD direction, the length direction was TD), the gauge length was 30 mm, the tensile speed was 50 mm / min, and the test environment was 23°C. In addition, the slope of the stress-strain curve at each strain was calculated using the least squares method of the regression line. In the calculation, one measurement point was used every 0.1 seconds, 10 points were used for the gradient of tensile strain from 0.05% to 0.25%, and 144 points were used for the gradient of tensile strain from 1% to 5%. The calculation method was the LINEST function of the spreadsheet software Microsoft Excel (Microsoft Corporation). The results are shown in Tables 2 and 3.
[0169] <Evaluation of molding curl at a molding depth of 8 mm> Each of the exterior materials for power storage devices obtained above was cut to prepare a rectangular piece of 150 mm in transverse direction (TD) × 90 mm in machine direction (MD), which was used as a test sample. The MD of the exterior material for power storage devices corresponds to the rolling direction (RD) of the aluminum alloy foil, and the TD of the exterior material for power storage devices corresponds to the TD of the aluminum alloy foil. A rectangular male mold of 31.6 mm × 54.5 mm (surface has a maximum height roughness (nominal value of Rz) of 1.6 μm as specified in Table 2 of the comparative surface roughness standard piece of JIS B 0659-1: 2002 Annex 1 (Reference), corner R2.0 mm, ridge R1.0 mm) with a clearance of 0.3 mm between the male mold and a female mold (surface has a maximum height roughness (nominal value of Rz) of 1.6 μm as specified in Table 2 of the comparative surface roughness standard piece of JIS B 0659-1: 2002 Annex 1 (Reference), corner R2.0 mm, ridge R1.0 mm) was cut into a rectangular shape. The maximum height roughness (nominal value of Rz) specified in Table 2 of the comparative surface roughness standard piece is 3.2 μm. Using a mold consisting of corner R2.0 mm, ridge R1.0 mm), the test sample was placed on the female mold so that the heat-sealable resin layer was located on the male mold side, and the test sample was pressed with a pressing pressure (surface pressure) of 0.25 MPa so that the test sample had a size of 31.6 mm (MD) x 54.5 mm (TD) and a molding depth of 8 mm, and cold-molded (pulled-in one-stage molding). Details of the position where molding was performed are as shown in FIG. 5. As shown in FIG. 5, molding was performed at a position where the shortest distance d between the rectangular molded part M and the end P of the test sample (exterior material 10 for power storage devices) was 70.5 mm. Next, the molded test sample (exterior material 10 for an electricity storage device) was placed on a horizontal surface 20 as shown in Fig. 6, and the maximum distance t in the vertical direction y from the horizontal surface 20 to the end P was taken as the maximum height of the curled portion. The maximum heights of 10 test samples were measured with a Digimatic Height Gauge (HD-30AX, manufactured by Mitutoyo Corporation), and the average value was taken as the molding curl. The results are shown in Table 2.
[0170] <Evaluation of moldability> Each of the exterior materials for power storage devices obtained above was cut into a rectangle with a length (MD) of 90 mm and a width (TD) of 150 mm to prepare a test sample. The MD of the exterior material for power storage devices corresponds to the rolling direction (RD) of the aluminum alloy foil, and the TD of the exterior material for power storage devices corresponds to the TD of the aluminum alloy foil. The test sample was placed in an environment of 25°C in a rectangular mold (female mold, surface has a maximum height roughness (nominal value of Rz) of 3.2 μm as specified in Table 2 of the comparative surface roughness standard piece of JIS B 0659-1:2002 Annex 1 (Reference), corner R2.0 mm, ridge R1.0 mm) in a plan view and a mold corresponding to the same (male mold, surface has a maximum height roughness (nominal value of Rz) of 3.2 μm as specified in Table 2 of the comparative surface roughness standard piece of JIS B 0659-1:2002 Annex 1 (Reference)). The maximum height roughness (nominal value of Rz) specified in Table 2 of the comparative surface roughness standard piece is 1.6 μm. Using a corner R2.0 mm, ridge R1.0 mm), the pressing pressure (surface pressure) was 0.25 MPa, and the molding depth was changed in 0.5 mm increments from the molding depth of 0.5 mm, and cold forming (one-stage drawing) was performed on 10 samples each to form a rectangular storage section (storage device element storage section) in plan view. At this time, the test sample was placed on the female mold so that the heat-sealable resin layer side was located on the male mold side and molding was performed. In addition, the clearance between the male mold and the female mold was 0.3 mm. The sample after cold forming was irradiated with light from a penlight in a dark room to confirm whether pinholes or cracks were generated in the aluminum alloy foil by light transmission. The deepest forming depth at which no pinholes or cracks occurred in the aluminum alloy foil among all 10 samples was defined as A mm, and the number of samples at which pinholes or the like occurred in the aluminum alloy foil at the shallowest forming depth was defined as B. The value calculated by the following formula was rounded off to two decimal places to determine the limit forming depth of the exterior material for electricity storage devices. The results are shown in Table 6. Limit forming depth = A mm + (0.5 mm / 10 pieces) x (10 pieces - B pieces)
[0171] [Table 2]
[0172] In Table 2, the value of the slope of the stress-strain (MPa) is the value obtained by rounding the first decimal place of the measured value. Also, the value of the forming curl is the value obtained by rounding the second decimal place of the measured value.
[0173] [Table 3]
[0174] In Table 3, the value of the slope of the stress-strain (MPa) is the value obtained by rounding the first decimal place of the measured value.
[0175] As shown in Table 2, for the exterior materials for power storage devices of Examples 1 to 13, the slope of the stress-strain curve corresponding to the two strain points of 1% and 5% tensile strain in the MD direction is within a specific range of 700 MPa or less. Despite the forming depth of the exterior materials for power storage devices of Examples 1 to 13 being as deep as 8 mm, the forming curl was suppressed and was less than 35 mm. On the other hand, for the exterior materials for power storage devices of Comparative Examples 1 and 2, the slope of the stress-strain curve corresponding to the two strain points of 1% and 5% tensile strain in the MD direction is outside the range of 700 MPa or less. Since the forming depth of the exterior materials for power storage devices of Comparative Examples 1 and 2 was as deep as 8 mm, the forming curl exceeded 35 mm. As shown in Table 3, regarding the slope of the stress-strain curve corresponding to the two strain points of 0.05% and 0.25% tensile strain in the MD direction, for example, Examples 6, 9 to 11 were 4311 to 6373 MPa, which were much larger values than those of Comparative Examples 1 and 2. However, the forming curl was more suppressed than that of Comparative Examples 1 and 2, and no clear correlation could be found between the tensile elastic modulus and the forming curl.
[0176] <Evaluation of forming curl at a forming depth of 8 mm with MD as the long side> The curl at a forming depth of 8 mm was measured in the same manner as in the above <Evaluation of curl at a forming depth of 8 mm>, except that, in the above <Evaluation of curl at a forming depth of 8 mm>, strips of MD 150 mm x TD 90 mm were prepared from the exterior materials for power storage devices obtained in Examples 1, 4, and 11, respectively, to serve as test samples, and that the molding using a mold was also performed by cold forming to a size of 31.6 mm (TD) x 54.5 mm (MD). The results are shown in Table 4.
[0177] [Table 4]
[0178] In Table 4, the forming curl values are each measured and rounded off to one decimal place.
[0179] From the results shown for Examples 1, 4, and 11 in Table 4, it can be seen that the forming curl when MD is the long side is larger than the forming curl shown in Examples 1, 4, and 11 shown in Table 2, and that when the exterior material for an electricity storage device is applied to an electricity storage device, it is more preferable to use it so that the long side direction of the storage section having a rectangular shape in a planar view corresponds to the TD direction of the exterior material for an electricity storage device.
[0180] <Evaluation of molding curl at a molding depth of 6 mm> Except for the fact that the molding depth was set to a shallow 6 mm, the molding curl at a molding depth of 6 mm was measured for the exterior packaging materials for electricity storage devices obtained in Examples 9, 10, and 11 in the same manner as in <Evaluation of molding curl at a molding depth of 8 mm> above. The results are shown in Table 5.
[0181] [Table 5]
[0182] In Table 5, the forming curl values are each measured and rounded off to one decimal place.
[0183] From the results of Examples 9 to 11 shown in Table 5, when the forming depth is shallow at 6 mm, the forming curl is smaller than when the forming depth is deep at 8 mm as shown in Table 2. As can be seen from these results, when experiments are performed with a small forming depth, problems related to forming curl are less likely to occur, and therefore it is difficult to recognize the problem of forming curl caused by increasing the forming depth.
[0184] [Table 6]
[0185] As described above, the present disclosure provides the following aspects of the invention. Item 1. The laminate is made of at least a base layer, a barrier layer, and a heat-sealable resin layer in this order. The laminate is an exterior material for an electricity storage device, in which the gradient of a stress-strain curve corresponding to two strain points of 1% tensile strain and 5% tensile strain in the MD direction is 700 MPa or less. Item 2. The exterior material for an electricity storage device according to Item 1, wherein the laminate has a slope of a stress-strain curve corresponding to two strain points of 1% tensile strain and 5% tensile strain in the TD direction of 630 MPa or less. Item 3. The exterior material for an electricity storage device according to Item 1 or 2, wherein an absolute value of a difference between a slope of a stress-strain curve corresponding to two strain points of tensile strain 1% and 5% in an MD direction of the laminate and a slope of a stress-strain curve corresponding to two strain points of tensile strain 1% and 5% in a TD direction of the laminate is 118 MPa or less. Item 4. An adhesive layer is provided between the barrier layer and the heat-sealable resin layer, Item 4. The exterior material for an electricity storage device according to any one of items 1 to 3, wherein the adhesive layer has a thickness of 10 μm or less. Item 5. The exterior packaging material for an electricity storage device according to any one of Items 1 to 4, wherein the base layer is constituted by a single layer of a polyamide film. Item 6. The packaging material for an electricity storage device according to any one of Items 1 to 5, further comprising a surface coating layer on the opposite side of the base material layer to the thermally adhesive resin layer side. Item 7. An electricity storage device, comprising an electricity storage device element including at least a positive electrode, a negative electrode, and an electrolyte, housed in a package formed from the exterior material for an electricity storage device according to any one of Items 1 to 6. Item 8. The storage portion of the package for storing the electricity storage device element has a rectangular shape in a plan view, Item 8. The electricity storage device according to item 7, wherein a long side direction of the storage unit corresponds to a TD direction of the exterior material for an electricity storage device. Item 9. The method includes a step of laminating at least a base layer, a barrier layer, and a heat-sealable resin layer in this order to obtain a laminate, A method for producing an exterior material for an electricity storage device, wherein the laminate has a gradient of a stress-strain curve corresponding to two strain points of 1% tensile strain and 5% tensile strain in the MD direction of 700 MPa or less. [Explanation of symbols]
[0186] 1 Base material layer 2 Adhesive layer 3. Barrier layer 4 Heat-fusible resin layer 5 Adhesive layer 6 Surface coating layer 10. Exterior materials for power storage devices 100 packages 100a: Storage section for electric storage device element
Claims
1. The laminate includes at least a base layer, a barrier layer, and a heat-sealable resin layer in this order. The laminate has a stress-strain curve having a slope in the MD direction between two strain points of 1% tensile strain and 5% tensile strain of 290 MPa or more and 700 MPa or less; An exterior material for an electricity storage device, wherein the absolute value of the difference between the slope of a stress-strain curve corresponding to two strain points of tensile strain 1% and 5% in the MD direction of the laminate and the slope of a stress-strain curve corresponding to two strain points of tensile strain 1% and 5% in the TD direction of the laminate is 118 MPa or less.
2. 2 . The exterior material for an electricity storage device according to claim 1 , wherein the barrier layer has a thickness of more than 50 μm and not more than 200 μm, and the base layer has a thickness of 2 μm or more and 25 μm or less.
3. 3. The exterior material for an electricity storage device according to claim 1, wherein the barrier layer has a thickness of more than 25 μm and not more than 50 μm, and the total thickness of layers inside the barrier layer is 24 μm or more and 34 μm or less.
4. The exterior material for an electricity storage device according to any one of claims 1 to 3, wherein the base material layer is a single layer.
5. The packaging material for an electricity storage device according to claim 4 , wherein the base layer is formed of a polyester film.
6. The exterior material for a storage battery device according to any one of claims 1 to 5, which is composed of a laminate including at least a surface coating layer, the base material layer, the barrier layer, an adhesive layer, and the heat-fusible resin layer in this order.
7. The exterior material for an electricity storage device according to any one of claims 1 to 5, further comprising a surface coating layer on the opposite side of the base material layer to the barrier layer side.
8. The exterior material for an electricity storage device according to claim 6 or 7, wherein the surface coating layer contains an additive.
9. The exterior material for an electricity storage device according to claim 8 , wherein the additive includes at least one of an organic substance and an inorganic substance.
10. The exterior material for an electricity storage device according to claim 9 , wherein the inorganic substance comprises at least one selected from the group consisting of silica, kaolin, barium sulfate, and titanium oxide.
11. The exterior material for an electricity storage device according to any one of claims 1 to 10, further comprising a colored adhesive layer between the base material layer and the barrier layer.
12. The exterior material for an electricity storage device according to any one of claims 1 to 11, further comprising a colored layer between the base layer and the barrier layer.
13. The packaging material for an electricity storage device according to any one of claims 1 to 12, wherein at least one surface of the barrier layer has a corrosion-resistant coating.
14. When the corrosion-resistant film was analyzed using time-of-flight secondary ion mass spectrometry, it was found that + and Cr + The exterior material for an electricity storage device according to claim 13, in which a peak derived from at least one of the above is detected.
15. The packaging material for an electricity storage device according to claim 13 or 14, wherein the corrosion-resistant coating contains at least one compound selected from the group consisting of a phosphorus compound salt, a chromium compound, a fluorine compound, and a triazine thiol compound.
16. An electricity storage device, comprising: an electricity storage device element having at least a positive electrode, a negative electrode, and an electrolyte; and the electricity storage device element is housed in a package formed from the exterior material for an electricity storage device according to any one of claims 1 to 15.
17. The housing portion of the packaging body for the electric storage device element has a rectangular shape in a plan view, The electricity storage device according to claim 16 , wherein a long side direction of the storage section corresponds to a TD direction of the exterior material for an electricity storage device.
18. The method includes a step of laminating at least a base layer, a barrier layer, and a heat-sealable resin layer in this order to obtain a laminate, The laminate has a stress-strain curve having a slope in the MD direction between two strain points of 1% tensile strain and 5% tensile strain of 290 MPa or more and 700 MPa or less; A method for producing an exterior material for an electricity storage device, wherein the absolute value of the difference between the slope of a stress-strain curve corresponding to two strain points of tensile strain 1% and 5% in the MD direction of the laminate and the slope of a stress-strain curve corresponding to two strain points of tensile strain 1% and 5% in the TD direction of the laminate is 118 MPa or less.
Citation Information
Patent Citations
Multilayer film, package material, and battery
JP2015107583A
Multilayer film, multilayer film package material, draw molded article, and battery
JP2015107585A
Polyester film, complex of the film and metal foil, and formation made by putting sealant layer on the complex
JP2015131888A
Packaging material and cell
WO2017131155A1
Layered package material, outer package material for battery, and the battery
JP2008287971A